Relationship between positional obstructive sleep apnea and excessive daytime sleepiness in patients with atrial fibrillation - Xiaoyue Liu; Patrick Stafford; Kenneth Bilchick; Sula Mazimba; Jeongok Logan; Yeilim Cho; Paras Patel; McCall Walker; William Healy; Younghoon Kwon (Sleep and Biological Rhythms, 2026)

Predicting the probability of concentrated flow occurrence using a dynamic approach on high-resolution soil surface data - Sayjro K. Nouwakpo; Osama Al-Hamdan; Christopher J. Williams; Kenneth Spaeth (CATENA, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The long march towards testing the adenosine receptor agonism hypothesis for human cerebroprotection: The story of the A1R/A3R receptor agonist AST-004 - Theodore E. Liston; William S. Korinek; Kenneth A. Jacobson; James D. Lechleiter (Purinergic Signalling, 2026)

High‐throughput multispecies quantitative polymerase chain reaction assays to study the effects of acute thermal stress in three species of Acipenser sturgeon - Hossein Haghighi; Kyle Madden; William S. Bugg; Faith M. Penny; Scott A. Pavey; Nicholas J. Bernier; Kenneth M. Jeffries (Journal of Fish Biology, 2026)
Fishes experience thermal stress in their natural environment that can be caused by natural or anthropogenic factors and can directly affect their physiology. In this study, we developed a multispecies OpenArray™ qPCR (quantitative polymerase chain reaction) ‘chip’ to measure the effects of acute thermal stress on the mRNA response of Acipenser sturgeons. The qPCR chips were then tested on three species: Acipenser fulvescens , Acipenser oxyrinchus and Acipenser brevirostrum. The A. fulvescens were from two genetically distinct populations (Burntwood River and Winnipeg River, Manitoba, Canada) that were acclimated to three different temperatures (16, 20 and 24°C) to quantify the effects of genetic background and acclimation temperatures on the transcriptomic response to acute thermal stress. Additionally, juvenile A. oxyrinchus oxyrinchus and A. brevirostrum were acclimated to 10°C and then experienced acute thermal stress. All three species were sampled for gill and liver before and after experiencing acute thermal stress, which was applied using a CT max test. The expression of 52 genes of interest was quantified using the multispecies qPCR chip for all three species, along with four reference genes. We showed that acute thermal stress affected the mRNA expression of 17–26 of the thermal metabolic stress genes that were assayed using the chip, depending on the species. However, the mRNA patterns varied between species and genetically distinct populations, suggesting differences in cellular responses to thermal stress that can lead to different susceptibilities to thermal stress in their natural habitats.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Precipitation variability interacts with mean precipitation to restructure a semiarid grassland community - Jennifer A. Rudgers; Laureano A. Gherardi; Purbendra Yogi; Melissa Bacigalupa; Tom E. X. Miller; Jacob J. Blais; Lana Bolin; Scott L. Collins; Enqing Hou; Yiqi Luo; Javier O. Morales; William T. Pockman; et al. (Ecology, 2026)
Climate forecasts project change not only in the mean of climate variables but also in their variance. If these dual changes interact, then future ecological dynamics will be difficult to predict using current experimental approaches, which typically change the mean or impose a single extreme event, such as drought. We designed a new field experiment to factorially reduce mean precipitation and increase its interannual variability. Across 4 years, drier, more variable precipitation additively reduced aboveground primary productivity by 48%–69% and interactively reduced the dominant plant species, but had no effect on the plant species predicted to dominate in the future, which could lead to state transition. Drier, more variable precipitation also interactively reduced biodiversity more than either climate factor alone, with 37%–42% fewer plant species than under ambient conditions, a pattern that matched declining richness during the past 20 years of ongoing climate change. Drier, more variable precipitation restructured the composition and spatiotemporal variation of the plant community. Altered precipitation mean or variance affected 14% of plant species, with eight species sensitive to the mean × variance interaction. Results suggest that future forecasts of plant community structure may be inadequate if they fail to incorporate climate mean × variance interactions.

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vertebral deformities in wild and farmed European plaice (Pleuronectes platessa) - Per Gunnar Fjelldal; Lucia Drábiková; Audun Østby Pedersen; Bahar Eldemir; Marina Mihalevic; Thomas William Kenneth Fraser; Ozlem Yilmaz (Aquaculture, 2026)

Emerging organic pollutants in sediments from Lake Victoria: Spatial patterns, sources and ecological risks - Merolyne Natuhwera; Patrick Ssebugere; Kenneth Arinaitwe; Peter Oswald; Edward Mubiru; Florence Nantaba; Zaccheus Shehu; Krištof Urban; Liudmyla Khvalbota; Nikiforos A. Alygizakis; Nikolaos S. Thomaidis; Dimitrios Triantafyllos Gerokonstantis; et al. (Science of The Total Environment, 2026)

Runoff and soil erosion on woodland-encroached sagebrush rangeland under simulated rainfall and concentrated flow conditions - Viktor O. Polyakov; C. Jason Williams; Justin C. Johnson; Erin L. Phelps; Raven Chavez; Philip Heilman; William A. Rutherford; Osama Z. Al-Hamdan; Sayjro K. Nouwakpo; Jia Hu; Kenneth E. Spaeth; Samuel Anderson (CATENA, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Inter-comparison of soybean models for simulation of evapotranspiration under rainfed and irrigated conditions - Kritika Kothari; Andrew Suyker; Rafael Battisti; Kenneth J. Boote; Sotirios Archontoulis; Julie Constantin; Santiago V. Cuadra; Philippe Debaeke; Elvis F. Elli; Babacar Faye; David Fleisher; Brian Grant; et al. (Agricultural and Forest Meteorology, 2026)

The Analysis of Transitional or Caudal Vertebrae Is Equally Suitable to Determine the Optimal Dietary Phosphorus Intake to Ensure Skeletal Health and Prevent Phosphorus Waste in Salmonid Aquaculture - Mursal Abdulkadir Hersi; Thomas William Kenneth Fraser; Saskia Kröckel; Per Gunnar Fjelldal; Lucia Drábiková (Fishes, 2025)
A prolonged dietary phosphorus (P) deficiency can result in reduced growth and vertebral deformities in farmed Atlantic salmon (Salmo salar). Severe deformities can impair swimming and lead to chronic stress associated with muscular fibrotic scarring. Conversely, excess dietary P contributes to farm effluents and environmental pollution. Vertebral centra ash content and mechanical strength both respond rapidly to suboptimal dietary P supply, but measuring all of salmon’s 59 vertebrae is time consuming. As such, this study assessed whether vertebrae from two commonly assessed regions (transitional and caudal) vary in their response to different dietary P levels. Atlantic salmon with an initial average weight of 1.8 kg (December 2022) were fed one of four experimental diets containing an increasing level of inorganic P (6.1–10.7 g/kg total P, 2.3–5.8 g/kg available P). Animals were distributed across 16 sea cages in a quadruplicated design. The regional differences in vertebral centra were assessed at two sampling points: in April 2023 following a slow growth period, and in July 2023 following a fast growth period. The growth of the caudal vertebrae in length surpassed the extension of the transitional vertebrae during the fast growth period. The bone mineralisation measured through vertebral centra ash and mechanical strength was however comparable between the regions, indicating that the rate of mineralisation was adjusted to the growth of the vertebrae. Only two parameters, yield point, which specifies the amount of energy that vertebra can absorb before it is permanently compressed, and toughness, a measure of stress per unit volume required to cause a fracture, showed regional differences. Considering transitional vertebrae, the estimated requirements were 4.1 g/kg available P in April and 4.4 g/kg in July, while the requirements based on caudal vertebrae were 3.7 g/kg in April and 4.6 g/kg in July. As such, both the transitional and caudal regions are equally suitable for a prompt recognition of suboptimal dietary P levels.

Progress, challenges and future directions in marine organic-walled dinoflagellate cyst research: New insights from an international workshop - Iria García-Moreiras; Ana Amorim; Vera Pospelova; Karin Zonneveld; Donald M. Anderson; Girish Beedessee; Amy Dale; Barrie Dale; Ophélie David; Anne de Vernal; Eugenia Fatourou; Emilie Folie-Boivin; et al. (Marine Micropaleontology, 2025)

Comment on Murphy et al. response to: Reassessing the drivers of capelin recruitment in Newfoundland since 1991 - Kenneth T. Frank; William C. Leggett (Fisheries Research, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Reassessing the drivers of capelin recruitment in Newfoundland since 1991 - Kenneth T. Frank; William C. Leggett (Fisheries Research, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Personal exposures to air pollutants and respiratory health among brick kiln workers and household members - Laura Nicolaou; Evelyn Rowell; Chelsea Gaviola; Ram K. Chandyo; Arun K. Sharma; Laxman P. Shrestha; Santa Das; David L. Parker; Steven M. Thygerson; Joseph Jacob; Bojidar Rangelov; Ryoko Egashira; et al. (Environmental Research, 2025)

Reducing UVR Exposure in Pregnant Women and Infants: A Pilot Study - William J. Tanguy; Kenneth P. Tercyak; Yizhe Xu; Jonathan Chipman; Nathan Shen; Caroline Joung; Hannah L. Brady; Marcelo M. Sleiman; Douglas Grossman; Lauren H. Theilen; Yelena P. Wu (Journal of Cancer Education, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Modeling Wetland Resources for Spring Migratory Waterbirds Under Different Agricultural Management Scenarios in the Iowa Portion of the Prairie Pothole Region, USA - Mark E. Mitchell; Michael J. Anteau; Aaron T. Pearse; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; David Green; Kenneth J. Forshay (Wetlands, 2025)
Constructed water quality wetlands, designed to accept tile drainage and surface runoff, are a promising solution for reducing surface water nutrient loading from agricultural systems. In addition to their water quality benefits, these systems may also offset losses of migratory waterbird stopover sites resulting from historical and future agricultural drainage modernization. To assess this possibility, we developed spatially explicit habitat models informed with expert opinion to explore the: 1) potential of water quality wetlands to provide suitable stopover resources for waterbirds during spring migration; and 2) the extent these wetlands can offset likely losses of stopover resources due to drainage modernization. We focused our modeling on the Iowa portion of the Prairie Pothole Region of North America as it was a historically important area within this vital region for waterbirds, but it has experienced widespread subsurface drainage. Model results indicate that unmitigated drainage modernization is likely to have a large negative effect on spring migratory resources for dabbling ducks and shorebirds and minimal effect on diving ducks. Water quality wetland installations are likely to provide habitat for dabbling and diving ducks, but wetland installation is unlikely to completely offset habitat losses for dabbling ducks and shorebirds. Drainage modernization aside, our results indicate that water quality wetlands can address several environmental issues associated with agricultural expansion and intensification by improving water quality and providing wetland resources for waterbirds and other organisms. Field-scale research is needed to validate these results.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Fractionation during sediment winnowing drives divergent mass accumulation rates derived from 230Th and 3He on the Cocos Ridge - Iva Tomchovska; Frank J. Pavia; Jess F. Adkins; William M. Berelson; Matthew P. Quinan; Kenneth A. Farley (Geochimica et Cosmochimica Acta, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Reductions in exposures to simulated respiratory aerosols by a ceiling-mounted HEPA air filtration unit - William G. Lindsley; Raymond C. Derk; Jayme P. Coyle; Francoise M. Blachere; Theresa Boots; Stephen B. Martin; Kenneth R. Mead; John D. Noti (Building and Environment, 2025)

Benthic community heterogeneity on the Eastern Antarctic continental shelf - Candace J. Grimes; Andrew R. Mahon; Kyle B. Donnelly; William Farris; Madison Gott; Coral Halanych; Conor Judge; Harrison I. Mancke; Nusrat J. Noor; Samantha A. Schreiter; Lindsay Uzarski; Jessica R. Zehnpfennig; et al. (Polar Biology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Radially-azimuthally discretized blade-element momentum theory for skewed coaxial turbines - Vinson Oliver Williams; Saurabh Agrawal; Kenneth Granlund; Andre P. Mazzoleni; Matthew Bryant (Ocean Engineering, 2025)

Spatiotemporal distribution patterns of large and medium-sized mammals in a biodiversity hotspot: mplications for conservation - Wenqiang Hu; Xueyou Li; Kenneth Otieno Onditi; Hongjiao Wang; Wenyu Song; Zhechang Hu; Changzhe Pu; Mingjing Pu; Yun Xiong; Suhua Yang; Lin Zhu; Jianqiang Yin; et al. (Biological Conservation, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Predicting sweetpotato traits using machine learning: Impact of environmental and agronomic factors on shape and size - Hangjin Liu; Shelly Hunt; G. Craig Yencho; Kenneth V. Pecota; Russell Mierop; Cranos M. Williams; Daniela S. Jones (Computers and Electronics in Agriculture, 2024)

The digital revolution in veterinary pathology - Kenneth Ancheta; Sophie Le Calvez; Jonathan Williams (Journal of Comparative Pathology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Evaluating spectral properties of invasive plant species in Kentucky recreation areas - William C. Lyons; Buddhi R. Gyawali; Richard Cristan; Shikha Acharya; Maheteme Gebremedhin; Kenneth Andries (International Journal of Remote Sensing, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Forest carbon uptake as influenced by snowpack and length of photosynthesis season in seasonally snow-covered forests of North America - Julia C. Yang; David R. Bowling; Kenneth R. Smith; Lewis Kunik; Brett Raczka; William R.L. Anderegg; Michael Bahn; Peter D. Blanken; Andrew D. Richardson; Sean P. Burns; Gil Bohrer; Ankur R. Desai; et al. (Agricultural and Forest Meteorology, 2024)

Old-Aged groundwater contributes to mountain hillslope hydrologic dynamics - Nicholas E. Thiros; Erica R. Siirila-Woodburn; Matthias Sprenger; Kenneth H. Williams; James P. Dennedy-Frank; Rosemary W.H. Carroll; W.P. Gardner (Journal of Hydrology, 2024)

Shifting groundwater fluxes in bedrock fractures: Evidence from stream water radon and water isotopes - Keira Johnson; John N. Christensen; W. Payton Gardner; Matthias Sprenger; Li Li; Kenneth H. Williams; Rosemary W.H. Carroll; Nicholas Thiros; Wendy Brown; Curtis Beutler; Alexander Newman; Pamela L. Sullivan (Journal of Hydrology, 2024)

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Can we reliably detect adaptive responses of hunter-gatherers to past climate change? Examining the impact of Mid-Holocene drought on Archaic settlement in the Basin-Plateau Region of North America - Brian F. Codding; Heidi Roberts; William Eckerle; Simon C. Brewer; Ishmael D. Medina; Kenneth B. Vernon; Jerry S. Spangler (Quaternary International, 2024)

Wastewater based surveillance can be used to reduce clinical testing intensity on a university campus - Ayaaz Amirali; Kristina M. Babler; Mark E. Sharkey; Cynthia C. Beaver; Melinda M. Boone; Samuel Comerford; Daniel Cooper; Benjamin B. Currall; Kenneth W. Goodman; George S. Grills; Erin Kobetz; Naresh Kumar; et al. (Science of The Total Environment, 2024)

A review of ecosystem services from edge-of-field practices in tile-drained agricultural systems in the United States Corn Belt Region - Mark E. Mitchell; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; Kenneth J. Forshay (Journal of Environmental Management, 2023)

Is the Coral Triangle’s future shown in a Pliocene reef gap? - G. William M. Harrison; Nadia Santodomingo; Kenneth G. Johnson; Willem Renema (Coral Reefs, 2023)
Although Pliocene temperature and pCO2 are similar to those predicted in the IPPC RCP4.5 scenario, the distribution of coral reefs in the center of maximum coral diversity, the Coral Triangle, during this period has not been explored. We discovered a significantly lower occurrence of reefs during the Pliocene, which we refer to as the Pliocene Reef Gap, but this decrease was not associated with a drop in coral genus richness. While some of the multiple local causes that drove this decline, such as sea level rise, are analogs to drivers of Anthropocene reef decline, neither warming nor increasing pCO2 are among them.

Red and melanized focal changes in white skeletal muscle in Atlantic salmon ( Salmo salar ): Comparative analysis of farmed, wild and hybrid fish reared under identical conditions - Malin Brimsholm; Per Gunnar Fjelldal; Tom Hansen; Thomas Kenneth William Fraser; Monica Solberg; Kevin Glover; Erling Olaf Koppang; Håvard Bjørgen (Journal of Fish Diseases, 2023)
Selective breeding plays a vital role in the production of farmed Atlantic salmon and has shown success in many aspects. Still, challenges related to fish health and welfare continue to result in significant economic losses. One such challenge is red and melanized focal changes (RFC/MFC), which result from acute and chronic inflammation, respectively, in the skeletal muscle. Importantly, RFC/MFC has not been observed in wild Atlantic salmon, suggesting that both external and genetic factors may contribute to the development of inflammation. To investigate the underlying cause of RFC/MFC, we conducted a study involving 1854 Atlantic salmon of farmed, wild and hybrid origin. All fish were reared under identical conditions to minimize the influence of external factors. Throughout the production cycle, the fish was monitored for growth parameters and examined for RFC/MFC using macroscopic and histological analysis. We found no association between the experimental groups and the presence of RFC/MFC. Histological investigations revealed melano‐macrophages in the soft tissue in freshwater smolt, although no macroscopic discoloration was observed. MFC showed granulomas in various stages, suggesting a complex progression of the condition. In summary, we conclude that RFC/MFC is primarily caused by external factors found in the rearing facilities of farmed Atlantic salmon.

A census of quality-controlled Biogeochemical-Argo float measurements - Adam C. Stoer; Yuichiro Takeshita; Tanya Lea Maurer; Charlotte Begouen Demeaux; Henry C. Bittig; Emmanuel Boss; Hervé Claustre; Giorgio Dall’Olmo; Christopher Gordon; Blair John William Greenan; Kenneth S. Johnson; Emanuele Organelli; et al. (Frontiers in Marine Science, 2023)
Biogeochemical- (BGC-) Argo aims to deploy and maintain a global array of autonomous profiling floats to monitor ocean biogeochemistry. With over 250,000 profiles collected so far, the BGC-Argo network is rapidly expanding toward the target of a sustained fleet of 1,000 floats. These floats prioritize the measurement of six key properties: oxygen, nitrate, pH, chlorophyll-a, suspended particles, and downwelling light. To assess the current biogeochemical state of the ocean, its variability, and trends with confidence, it is crucial to quality control these measurements. Accordingly, BGC-Argo maintains a quality control system using manual inspection and parameter-specific algorithms for flagging and adjusting data. In this study, we provide a census of the quantity and quality of measurements from BGC-Argo based on their quality flagging system. The purpose of this census is to assess the current status of the array in terms of data quality, how data quality has changed over time, and to provide a better understanding of the quality-controlled data to current and future users. Alongside increasing profile numbers and spatial coverage, we report that for most parameters between 80 and 95% of the profiles collected so far contain high-quality BGC data, with an exception for pH. The quality of pH profiles has seen a large improvement in the last five years and is on track to match the data quality of other BGC parameters. We highlight how BGC-Argo is improving and discuss strategies to increase the quality and quantity of BGC profiles available to users. This census shows that tracking percentages of high-quality data through time is useful for monitoring float sensor technology and helpful for ensuring the long-term success of BGC-Argo.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Whole genome assessment of a declining game bird reveals cryptic genetic structure and insights for population management - Leilton W. Luna; Lisa M. Williams; Kenneth Duren; Reina Tyl; David P. L. Toews; Julian D. Avery (Molecular Ecology, 2023)
Population genomics applied to game species conservation can help delineate management units, ensure appropriate harvest levels and identify populations needing genetic rescue to safeguard their adaptive potential. The ruffed grouse ( Bonasa umbellus ) is rapidly declining in much of the eastern USA due to a combination of forest maturation and habitat fragmentation. More recently, mortality from West Nile Virus may have affected connectivity of local populations; however, genetic approaches have never explicitly investigated this issue. In this study, we sequenced 54 individual low‐coverage (~5X) grouse genomes to characterize population structure, assess migration rates across the landscape to detect potential barriers to gene flow and identify genomic regions with high differentiation. We identified two genomic clusters with no clear geographic correlation, with large blocks of genomic differentiation associated with chromosomes 4 and 20, likely due to chromosomal inversions. After excluding these putative inversions from the data set, we found weak but nonsignificant signals of population subdivision. Estimated gene flow revealed reduced rates of migration in areas with extensive habitat fragmentation and increased genetic connectivity in areas with less habitat fragmentation. Our findings provide a benchmark for wildlife managers to compare and scale the genetic diversity and structure of ruffed grouse populations in Pennsylvania and across the eastern USA, and we also reveal structural variation in the grouse genome that requires further study to understand its possible effects on individual fitness and population distribution.

Impact of phenanthrene co-administration on the toxicokinetics of benzo[a]pyrene in humans. UPLC-accelerator mass spectrometry following oral microdosing - Monica L. Vermillion Maier; Lisbeth K. Siddens; Jamie M. Pennington; Sandra L. Uesugi; Edwin M. Labut; Emily A. Vertel; Kim A. Anderson; Lane G. Tidwell; Susan C. Tilton; Ted J. Ognibene; Kenneth W. Turteltaub; Jordan N. Smith; et al. (Chemico-Biological Interactions, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Biogeomorphology of Ireland's oldest fossil forest: Plant-sediment and plant-animal interactions recorded in the Late Devonian Harrylock Formation, Co. Wexford - Yorick P. Veenma; Neil S. Davies; Kenneth T. Higgs; William J. McMahon (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Lack of efflux of diglycolic acid from proximal tubule cells leads to its accumulation and to toxicity of diethylene glycol - Julie D. Tobin; Corie N. Robinson; Elliot S. Luttrell-Williams; Greg M. Landry; Kenneth E. McMartin (Toxicology Letters, 2023)

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Benzo[a]pyrene toxicokinetics in humans following dietary supplementation with 3,3′-diindolylmethane (DIM) or Brussels sprouts - Monica L. Vermillion Maier; Lisbeth K. Siddens; Jamie M. Pennington; Sandra L. Uesugi; Susan C. Tilton; Emily A. Vertel; Kim A. Anderson; Lane G. Tidwell; Ted J. Ognibene; Kenneth W. Turteltaub; Jordan N. Smith; David E. Williams (Toxicology and Applied Pharmacology, 2023)

Mineralogical, magnetic and geochemical data constrain the pathways and extent of weathering of mineralized sedimentary rocks - Sergio Carrero; Sarah P. Slotznick; Sirine C. Fakra; M. Cole Sitar; Sharon E. Bone; Jeffrey L. Mauk; Andrew H. Manning; Nicholas L. Swanson-Hysell; Kenneth H Williams; Jillian F. Banfield; Benjamin Gilbert (Geochimica et Cosmochimica Acta, 2023)

Efficacy of Do-It-Yourself air filtration units in reducing exposure to simulated respiratory aerosols - Raymond C. Derk; Jayme P. Coyle; William G. Lindsley; Francoise M. Blachere; Angela R. Lemons; Samantha K. Service; Stephen B. Martin; Kenneth R. Mead; Steven A. Fotta; Jeffrey S. Reynolds; Walter G. McKinney; Erik W. Sinsel; et al. (Building and Environment, 2023)

Medial Unicompartmental Knee Arthroplasty Restores Native Knee Kinematics During Activities of Daily Living: A Pilot Study - Venkata K. Byrapogu; Tom Gale; Brian Hamlin; Kenneth L. Urish; William Anderst (Annals of Biomedical Engineering, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Size-dependent analyses provide insights into the reproductive allocation and plasticity of invasive and native Typha - Emily E. Jameson; Kenneth Elgersma; Jason P. Martina; William S. Currie; Deborah E. Goldberg (Biological Invasions, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Phosphorylation-dependent proteome of Marcks in ependyma during aging and behavioral homeostasis in the mouse forebrain - Nagendran Muthusamy; Taufika I. Williams; Ryan O’Toole; Jon J. Brudvig; Kenneth B. Adler; Jill M. Weimer; David C. Muddiman; H. Troy Ghashghaei (GeroScience, 2022)

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Initial recovery of demersal fish communities in coastal waters of Hong Kong, South China, following a trawl ban - Yanny K. Y. Mak; Lily S. R. Tao; Valerie C. M. Ho; David Dudgeon; William W. L. Cheung; Kenneth M. Y. Leung (Reviews in Fish Biology and Fisheries, 2021)
Fisheries resources in Hong Kong have been overexploited since the 1970s due to intensive bottom trawling and other fishing activities that have depleted stocks and destroyed marine habitat. To rehabilitate depleted fisheries resources, a permanent ban on trawling in Hong Kong territorial waters came into force on December 31, 2012. In order to determine whether the trawl facilitated recovery of fish communities, trawl surveys were conducted at two sites in each of the eastern, southern and western (estuarine) coastal waters of Hong Kong before and three years after the trawl ban. A total of 315 species and 86 families of fishes in nine feeding groups were encountered during the surveys. Mean trophic level of the fish community, abundance and biomass of total fishes and of predatory fishes increased in eastern and western waters after the ban, but no changes or declines in these metrics were observed in southern waters. Although initial recovery in fish community were observed in eastern and western waters, anthropogenic disturbances might hinder the recovery process, including a large-scale reclamation for construction of coastal infrastructures in the west, illegal trawling, and expansion of non-trawling fishing efforts in the southern and eastern waters. Longer term monitoring is needed to evaluate the effects of the trawl ban, and determine whether recovery in the southern waters will continue to be constrained by the anthropogenic disturbances. Graphic abstract

The population genetics characteristics of a 90 locus panel of microhaplotypes - Andrew J. Pakstis; Neeru Gandotra; William C. Speed; Michael Murtha; Curt Scharfe; Kenneth K. Kidd (Human Genetics, 2021)
Single-nucleotide polymorphisms (SNPs) and small genomic regions with multiple SNPs (microhaplotypes, MHs) are rapidly emerging as novel forensic investigative tools to assist in individual identification, kinship analyses, ancestry inference, and deconvolution of DNA mixtures. Here, we analyzed information for 90 microhaplotype loci in 4009 individuals from 79 world populations in 6 major biogeographic regions. The study included multiplex microhaplotype sequencing (mMHseq) data analyzed for 524 individuals from 16 populations and genotype data for 3485 individuals from 63 populations curated from public repositories. Analyses of the 79 populations revealed excellent characteristics for this 90-plex MH panel for various forensic applications achieving an overall average effective number of allele values (A e ) of 4.55 (range 1.04–19.27) for individualization and mixture deconvolution. Population-specific random match probabilities ranged from a low of 10 –115 to a maximum of 10 –66 . Mean informativeness (I n ) for ancestry inference was 0.355 (range 0.117–0.883). 65 novel SNPs were detected in 39 of the MHs using mMHseq. Of the 3018 different microhaplotype alleles identified, 1337 occurred at frequencies > 5% in at least one of the populations studied. The 90-plex MH panel enables effective differentiation of population groupings for major biogeographic regions as well as delineation of distinct subgroupings within regions. Open-source, web-based software is available to support validation of this technology for forensic case work analysis and to tailor MH analysis for specific geographical regions.

Six weeks of high-intensity interval training enhances contractile activity induced vascular reactivity and skeletal muscle perfusion in older adults - Philip J. J. Herrod; Philip J. Atherton; Kenneth Smith; John P. Williams; Jonathan N. Lund; Bethan E. Phillips (GeroScience, 2021)
Impairments in muscle microvascular function are associated with the pathogenesis of sarcopenia and cardiovascular disease. High-intensity interval training (HIIT) is an intervention by which a myriad of beneficial skeletal muscle/cardiovascular adaptations have been reported across age, including capillarisation and improved endothelial function. Herein, we hypothesised that HIIT would enhance muscle microvascular blood flow and vascular reactivity to acute contractile activity in older adults, reflecting HIIT-induced vascular remodelling. In a randomised controlled-trial, twenty-five healthy older adults aged 65–85 years (mean BMI 27.0) were randomised to 6-week HIIT or a no-intervention control period of an equal duration. Measures of microvascular responses to a single bout of muscle contractions (i.e. knee extensions) were made in the m. vastus lateralis using contrast-enhanced ultrasound during a continuous intravenous infusion of Sonovue™ contrast agent, before and after the intervention period, with concomitant assessments of cardiorespiratory fitness and resting blood pressure. HIIT led to improvements in anaerobic threshold (13.2 ± 3.4 vs. 15.3 ± 3.8 ml/kg/min, P < 0.001), dynamic exercise capacity (145 ± 60 vs. 159 ± 59 W, P < 0.001) and resting (systolic) blood pressure (142 ± 15 vs. 133 ± 11 mmHg, P < 0.01). Notably, HIIT elicited significant increases in microvascular blood flow responses to acute contractile activity (1.8 ± 0.63 vs. 2.3 ± 0.8 (arbitrary contrast units (AU), P < 0.01)), with no change in any of these parameters observed in the control group. Six weeks HIIT improves skeletal muscle microvascular responsiveness to acute contractile activity in the form of active hyperaemia-induced by a single bout of resistance exercise. These findings likely reflect reports of enhanced large vessel distensibility, improved endothelial function, and muscle capillarisation following HIIT. Moreover, our findings illustrate that HIIT may be effective in mitigating deleterious alterations in muscle microvascular mediated aspects of sarcopenia.

Honorary Professor Garry Graham - Richard O. Day; Kenneth M. Williams; Kieran F. Scott (Inflammopharmacology, 2021)

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

Does a Trawl Ban Benefit Commercially Important Decapoda and Stomatopoda in Hong Kong? - Lily S. R. Tao; Gilbert C. S. Lui; Kingsley J. H. Wong; Tommy T. Y. Hui; Yanny K. Y. Mak; Ronia C.-t Sham; Jason K. C. Yau; William W. L. Cheung; Kenneth M. Y. Leung (Ecosystems, 2021)
Crustaceans were among the most valuable fishery resources in Hong Kong. However, the unrestricted and intensive use of different fishing gears, especially bottom trawling, has led to the depletion of commercially important crustaceans in Hong Kong since the 1980s. This study investigated whether commercial crustaceans recovered after the implementation of a permanent Hong Kong-wide trawl ban that began on December 31, 2012. Standardized field surveys were conducted using a commercial shrimp trawler at two sites in eastern and western waters of Hong Kong before (2004) and after the trawl ban (2013–2014 and 2015–2016) and two sites in southern waters after the trawl ban. Diversity, mean size, abundance, biomass and level of disturbance of commercial crustaceans from the three periods were investigated. The eastern waters exhibited an increased diversity of crustacean assemblages in Inner Tolo, and a higher abundance and biomass of crabs were detected in Outer Tolo after the trawl ban. Reduced disturbance, higher diversity in crustacean assemblages and greater abundance and biomass of predatory crabs were observed after the trawl ban in the outer estuary of western waters, and increased abundance and biomass of shrimp were detected in the inner estuary of western waters. No temporal or negative changes were detected in the southeast and southern waters of Lamma Island. The various responses of crustacean assemblages in Hong Kong waters revealed the critical role of complex interactions among multiple stresses, such as ongoing reclamation works, illegal trawling activities and increased fishing efforts using other (legal) fishing methods.

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Spatio‐temporal insights into microbiology of the freshwater‐to‐hypersaline, oxic‐hypoxic‐euxinic waters of Ursu Lake - Andreea Baricz; Cecilia Maria Chiriac; Adrian‐Ștefan Andrei; Paul‐Adrian Bulzu; Erika Andrea Levei; Oana Cadar; Karina Paula Battes; Mirela Cîmpean; Marin Șenilă; Adorján Cristea; Vasile Muntean; Mircea Alexe; et al. (Environmental Microbiology, 2021)
Summary Ursu Lake is located in the Middle Miocene salt deposit of Central Romania. It is stratified, and the water column has three distinct water masses: an upper freshwater‐to‐moderately saline stratum (0–3 m), an intermediate stratum exhibiting a steep halocline (3–3.5 m), and a lower hypersaline stratum (4 m and below) that is euxinic (i.e. anoxic and sulphidic). Recent studies have characterized the lake's microbial taxonomy and given rise to intriguing ecological questions. Here, we explore whether the communities are dynamic or stable in relation to taxonomic composition, geochemistry, biophysics, and ecophysiological functions during the annual cycle. We found: (i) seasonally fluctuating, light‐dependent communities in the upper layer (≥0.987–0.990 water‐activity), a stable but phylogenetically diverse population of heterotrophs in the hypersaline stratum (water activities down to 0.762) and a persistent plate of green sulphur bacteria that connects these two (0.958–0.956 water activity) at 3–3.5 to 4 m; (ii) communities that might be involved in carbon‐ and sulphur‐cycling between and within the lake's three main water masses; (iii) uncultured lineages including Acetothermia (OP1), Cloacimonetes (WWE1), Marinimicrobia (SAR406), Omnitrophicaeota (OP3), Parcubacteria (OD1) and other Candidate Phyla Radiation bacteria, and SR1 in the hypersaline stratum (likely involved in the anaerobic steps of carbon‐ and sulphur‐cycling); and (iv) that species richness and habitat stability are associated with high redox‐potentials. Ursu Lake has a unique and complex ecology, at the same time exhibiting dynamic fluctuations and stability, and can be used as a modern analogue for ancient euxinic water bodies and comparator system for other stratified hypersaline systems.

Brain tissue transcriptomic analysis of SIV-infected macaques identifies several altered metabolic pathways linked to neuropathogenesis and poly (ADP-ribose) polymerases (PARPs) as potential therapeutic targets - Carla Mavian; Andrea S. Ramirez-Mata; James Jarad Dollar; David J. Nolan; Melanie Cash; Kevin White; Shannan N. Rich; Brittany Rife Magalis; Simone Marini; Mattia C. F. Prosperi; David Moraga Amador; Alberto Riva; et al. (Journal of NeuroVirology, 2021)
Despite improvements in antiretroviral therapy, human immunodeficiency virus type 1 (HIV-1)-associated neurocognitive disorders (HAND) remain prevalent in subjects undergoing therapy. HAND significantly affects individuals’ quality of life, as well as adherence to therapy, and, despite the increasing understanding of neuropathogenesis, no definitive diagnostic or prognostic marker has been identified. We investigated transcriptomic profiles in frontal cortex tissues of Simian immunodeficiency virus (SIV)-infected Rhesus macaques sacrificed at different stages of infection. Gene expression was compared among SIV-infected animals ( n = 11), with or without CD8+ lymphocyte depletion, based on detectable ( n = 6) or non-detectable ( n = 5) presence of the virus in frontal cortex tissues. Significant enrichment in activation of monocyte and macrophage cellular pathways was found in animals with detectable brain infection, independently from CD8+ lymphocyte depletion. In addition, transcripts of four poly (ADP-ribose) polymerases (PARPs) were up-regulated in the frontal cortex, which was confirmed by real-time polymerase chain reaction. Our results shed light on involvement of PARPs in SIV infection of the brain and their role in SIV-associated neurodegenerative processes. Inhibition of PARPs may provide an effective novel therapeutic target for HIV-related neuropathology.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Nucleotide P2Y1 receptor agonists are in vitro and in vivo prodrugs of A1/A3 adenosine receptor agonists: implications for roles of P2Y1 and A1/A3 receptors in physiology and pathology - Theodore E. Liston; Sonja Hinz; Christa E. Müller; Deborah M. Holstein; Jay Wendling; Roger J. Melton; Mary Campbell; William S. Korinek; R. Rama Suresh; Dane A. Sethre-Hofstad; Zhan-Guo Gao; Dilip K. Tosh; et al. (Purinergic Signalling, 2020)

Phylogenomic analyses reveal a Palaeozoic radiation and support a freshwater origin for clitellate annelids - Christer Erséus; Bronwyn W. Williams; Kevin M. Horn; Kenneth M. Halanych; Scott R. Santos; Samuel W. James; Michel Creuzé des Châtelliers; Frank E. Anderson (Zoologica Scripta, 2020)
Clitellata is a major clade of Annelida comprising nearly all freshwater and terrestrial annelids as well as several marine species. We investigated clitellate phylogenetic relationships using transcriptomes sampled from 74 taxa (64 clitellates and 10 polychaetes), including multiple representatives of nearly all major clitellate higher taxa (Branchiobdellida, Capilloventridae, Crassiclitellata, Enchytraeidae, Haplotaxidae, Hirudinida, Lumbriculida, Moniligastridae, Naididae, Parvidrilidae, Phreodrilidae, Propappidae and Randiellidae). We used a number of filtered data matrices and phylogenetic analyses to examine the effects of data partitioning, missing data and compositional and branch‐length heterogeneity and used the resulting phylogenies for divergence time estimation and ancestral habitat reconstructions. All analyses and filtering methods produced a consistent, strongly supported topology in which (a) Enchytraeidae, Hirudinida, Hirudinea (here, Branchiobdellida plus Hirudinida), Lumbriculida, Lumbriculata (Lumbriculida plus Hirudinea), Phreodrilidae and Naididae are monophyletic, (b) a Parvidrilidae + Randiellidae clade is sister to the rest of Clitellata, (c) Phreodrilidae is sister to Naididae, (d) Haplotaxidae is non‐monophyletic, with some haplotaxids grouping with Crassiclitellata + Moniligastridae, (e) the Phreodrilidae + Naididae clade is sister to all other clitellates except Parvidrilidae + Randiellidae and Capilloventridae, and (f) Lumbriculata is sister to the Crassiclitellata + Moniligastridae + Haplotaxidae (in part) clade. Ancestral habitat reconstructions and divergence time analysis suggested that the most recent common ancestor of Clitellata lived in freshwater during the Devonian (419–359 million years ago) and that all major extant clitellate lineages arose over the next ~150 million years, with multiple lineages subsequently returning to marine habitats or invading land. This study provides a phylogenetic framework for further investigation of the geological, environmental and biotic forces and genomic changes that may have impacted clitellate evolution and enabled several major habitat transitions within this group.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Seasonal manganese transport in the hyporheic zone of a snowmelt-dominated river (East River, Colorado, USA) - Savannah R. Bryant; Audrey H. Sawyer; Martin A. Briggs; Casey M. Saup; Amelia R. Nelson; Michael J. Wilkins; John N. Christensen; Kenneth H. Williams (Hydrogeology Journal, 2020)

Correction to: Development of Decisional Values Statements for Lung Cancer Screening among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Development of Decisional Values Statements for Lung Cancer Screening Among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Correction to: Status and trends of circumpolar peregrine falcon and gyrfalcon populations - Alastair Franke; Knud Falk; Kevin Hawkshaw; Skip Ambrose; David L. Anderson; Peter J. Bente; Travis Booms; Kurt K. Burnham; Suzanne Carrière; Johan Ekenstedt; Ivan Fufachev; Sergey Ganusevich; et al. (Ambio, 2020)

Status and trends of circumpolar peregrine falcon and gyrfalcon populations - Alastair Franke; Knud Falk; Kevin Hawkshaw; Skip Ambrose; David L. Anderson; Peter J. Bente; Travis Booms; Kurt K. Burnham; Johan Ekenstedt; Ivan Fufachev; Sergey Ganusevich; Kenneth Johansen; et al. (Ambio, 2020)

Climate drives community‐wide divergence within species over a limited spatial scale: evidence from an oceanic island - Antonia Salces‐Castellano; Jairo Patiño; Nadir Alvarez; Carmelo Andújar; Paula Arribas; Juan José Braojos‐Ruiz; Marcelino del Arco‐Aguilar; Víctor García‐Olivares; Dirk N. Karger; Heriberto López; Ioanna Manolopoulou; Pedro Oromí; et al. (Ecology Letters, 2020)
Geographic isolation substantially contributes to species endemism on oceanic islands when speciation involves the colonisation of a new island. However, less is understood about the drivers of speciation within islands. What is lacking is a general understanding of the geographic scale of gene flow limitation within islands, and thus the spatial scale and drivers of geographical speciation within insular contexts. Using a community of beetle species, we show that when dispersal ability and climate tolerance are restricted, microclimatic variation over distances of only a few kilometres can maintain strong geographic isolation extending back several millions of years. Further to this, we demonstrate congruent diversification with gene flow across species, mediated by Quaternary climate oscillations that have facilitated a dynamic of isolation and secondary contact. The unprecedented scale of parallel species responses to a common environmental driver for evolutionary change has profound consequences for understanding past and future species responses to climate variation.

Estimating Mangrove Tree Biomass and Carbon Content: A Comparison of Forest Inventory Techniques and Drone Imagery - Alice R. Jones; Ramesh Raja Segaran; Kenneth D. Clarke; Michelle Waycott; William S. H. Goh; Bronwyn M. Gillanders (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Experimental drought reduces genetic diversity in the grassland foundation species Bouteloua eriopoda - Kenneth D. Whitney; Joann Mudge; Donald O. Natvig; Anitha Sundararajan; William T. Pockman; Jennifer Bell; Scott L. Collins; Jennifer A. Rudgers (Oecologia, 2019)

Inhibition of Sodium–Hydrogen Antiport by Antibodies to NHA1 in Brush Border Membrane Vesicles from Whole Aedes aegypti Larvae - Kenneth M. Sterling; William R. Harvey (The Journal of Membrane Biology, 2019)

Upstream Migration and Spawning Success of Chinook Salmon in a Highly Developed, Seasonally Warm River System - William P. Connor; Kenneth F. Tiffan; James A. Chandler; Dennis W. Rondorf; Billy D. Arnsberg; Kelvin C. Anderson (Reviews in Fisheries Science & Aquaculture, 2019)

Functional MRI and delay discounting in patients infected with hepatitis C - Holly McCready; Milky Kohno; Michael Kolessar; Laura Dennis; Daniel Kriz; Hannah Luber; Renee Anderson; Michael Chang; Anna Sasaki; Kenneth Flora; Arthur Vandenbark; Suzanne H. Mitchell; et al. (Journal of NeuroVirology, 2018)

Review of non-clinical risk models to aid prevention of breast cancer - Kawthar Al-Ajmi; Artitaya Lophatananon; Martin Yuille; William Ollier; Kenneth R. Muir (Cancer Causes & Control, 2018)

Correction to: An SIV macaque model of SIV and HAND: the need for adjunctive therapies in HIV that target activated monocytes and macrophages - Jaclyn Mallard; Kenneth Williams (Journal of NeuroVirology, 2018)

Correction to: A Semi-Physiologically Based Pharmacokinetic Model Describing the Altered Metabolism of Midazolam Due to Inflammation in Mice - Ninad Varkhede; Nita Patel; William Chang; Kenneth Ruterbories; M. Laird Forrest (Pharmaceutical Research, 2018)

A Semi-Physiologically Based Pharmacokinetic Model Describing the Altered Metabolism of Midazolam Due to Inflammation in Mice - Ninad Varkhede; Nita Patel; William Chang; Kenneth Ruterbories; M. Laird Forrest (Pharmaceutical Research, 2018)

Assessing the interplay between canopy energy balance and photosynthesis with cellulose δ18O: large-scale patterns and independent ground-truthing - Brent R. Helliker; Xin Song; Michael L. Goulden; Kenneth Clark; Paul Bolstad; J. William Munger; Jiquan Chen; Asko Noormets; David Hollinger; Steve Wofsy; Timothy Martin; Dennis Baldocchi; et al. (Oecologia, 2018)

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

Non-additive effects of air and water warming on an intertidal predator–prey interaction - William King; Kenneth P. Sebens (Marine Biology, 2018)

An SIV macaque model of SIV and HAND: the need for adjunctive therapies in HIV that target activated monocytes and macrophages - Jaclyn Mallard; Kenneth Williams (Journal of NeuroVirology, 2018)

Climatic variability of the Pacific and Atlantic Oceans and western US snowpack - Pratik Pathak; Ajay Kalra; Kenneth W. Lamb; William P. Miller; Sajjad Ahmad; Rajesh Amerineni; Devi P. Ponugoti (International Journal of Climatology, 2018)
This study examines the changing characteristics of snow water equivalent (SWE) in western United States and their teleconnections with large‐scale variability of the Pacific and Atlantic Oceans. This study evaluated the relationship among sea surface temperatures (SST), 500‐mbar geopotential height (Z 500 ), 500‐mbar east–west wind (U 500 ), and western United States SWE (1 March, 1 April, and 1 May). The averages of SST, Z 500 , and U 500 were computed to create a lead time of 2–10 months. Three different 6‐month series were computed – January–June, April–September, and July–December – and were correlated with SWE stations in the western United States. The study utilized singular‐value decomposition (SVD) for a period of 1961–2016 to correlate the SWE and climate indices. SVD was applied between the standardized SST and SWE to obtain their correlation and to evaluate connection with Z 500 and U 500 within the same SVD relationship. Specifically, SVD was not applied independently on each variable prior to this study. The correlations were observed to increase as the lead time decreased. First mode SVD showed a pronounced non‐El Niño‐Southern Oscillation short‐wave train for the July–December climate in the Z 500 data; this terminated over the Great Lakes region, and was strongly correlated with the warming of the SST near the east coast of Japan, resulting in decreased SWE in the study area. Second mode SVD showed a negative correlation between SWE stations in Colorado and Utah and SST near the Asian and Australian continents. The associations between climate indices and SWE that were identified during this study could be used to improve long‐term forecasts, resulting in better management of water resources in the region.

A Maize Inbred Exhibits Resistance Against Western Corn Rootwoorm, Diabrotica virgifera virgifera - Lina Castano-Duque; Kenneth W. Loades; John F. Tooker; Kathleen M. Brown; W. Paul Williams; Dawn S. Luthe (Journal of Chemical Ecology, 2017)

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

An oral form of methylglyoxal-bis-guanylhydrazone reduces monocyte activation and traffic to the dorsal root ganglia in a primate model of HIV-peripheral neuropathy - Jessica R. Lakritz; Samshita Yalamanchili; Michael J. Polydefkis; Andrew D. Miller; Michael S. McGrath; Kenneth C. Williams; Tricia H. Burdo (Journal of NeuroVirology, 2017)

Hong Kong’s rich marine biodiversity: the unseen wealth of South China’s megalopolis - Terence P. T. Ng; Martin C. F. Cheng; Kevin K. Y. Ho; Gilbert C. S. Lui; Kenneth M. Y. Leung; Gray A. Williams (Biodiversity and Conservation, 2017)

Site-level importance of broadleaf deciduous trees outweighs the legacy of high nitrogen (N) deposition on ecosystem N status of Central Appalachian red spruce forests - Kenneth R. Smith; Justin M. Mathias; Brenden E. McNeil; William T. Peterjohn; Richard B. Thomas (Plant and Soil, 2016)

Measuring Microhabitat Temperature in Arboreal Primates: A Comparison of On-Animal and Stationary Approaches - Cynthia L. Thompson; Susan H. Williams; Kenneth E. Glander; Christopher J. Vinyard (International Journal of Primatology, 2016)

Orchid historical biogeography, diversification, Antarctica and the paradox of orchid dispersal - Thomas J. Givnish; Daniel Spalink; Mercedes Ames; Stephanie P. Lyon; Steven J. Hunter; Alejandro Zuluaga; Alfonso Doucette; Giovanny Giraldo Caro; James McDaniel; Mark A. Clements; Mary T. K. Arroyo; Lorena Endara; et al. (Journal of Biogeography, 2016)
Aim Orchidaceae is the most species‐rich angiosperm family and has one of the broadest distributions. Until now, the lack of a well‐resolved phylogeny has prevented analyses of orchid historical biogeography. In this study, we use such a phylogeny to estimate the geographical spread of orchids, evaluate the importance of different regions in their diversification and assess the role of long‐distance dispersal ( LDD ) in generating orchid diversity. Location Global. Methods Analyses use a phylogeny including species representing all five orchid subfamilies and almost all tribes and subtribes, calibrated against 17 angiosperm fossils. We estimated historical biogeography and assessed the importance of different regions for rates of speciation, extinction and net species diversification. We evaluated the impact of particular LDD events on orchid diversity by asking how many species evolved in the new range subsequent to those events. Results Orchids appear to have arisen in Australia 112 Ma (95% higher probability distribution: 102.0–120.0 Ma), then spread to the Neotropics via Antarctica by 90 Ma ( HPD : 79.7–99.5 Ma), when all three continents were in close contact and apostasioids split from the ancestor of all other orchids. Ancestors of vanilloids, cypripedioids and orchidoids+epidendroids appear to have originated in the Neotropics 84–64 Ma. Repeated long‐ and short‐distance dispersal occurred through orchid history: stochastic mapping identified a mean total of 74 LDD events or 0.8 Ma −1 . Across orchid history, Southeast Asia was the most important source and maximally accelerated net diversification; across epidendroids, the Neotropics maximally accelerated diversification. Main conclusions Our analysis provides the first biogeographical history of the orchids, implicating Australia, the Neotropics and Antarctica in their origin. LDD and life in the Neotropics – especially the Andes – had profound effects on their spread and diversification; > 97% of all orchid species are restricted to individual continents.

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

Critical biogeochemical functions in the subsurface are associated with bacteria from new phyla and little studied lineages - Laura A. Hug; Brian C. Thomas; Itai Sharon; Christopher T. Brown; Ritin Sharma; Robert L. Hettich; Michael J. Wilkins; Kenneth H. Williams; Andrea Singh; Jillian F. Banfield (Environmental Microbiology, 2016)
Summary Nitrogen, sulfur and carbon fluxes in the terrestrial subsurface are determined by the intersecting activities of microbial community members, yet the organisms responsible are largely unknown. Metagenomic methods can identify organisms and functions, but genome recovery is often precluded by data complexity. To address this limitation, we developed subsampling assembly methods to re‐construct high‐quality draft genomes from complex samples. We applied these methods to evaluate the interlinked roles of the most abundant organisms in biogeochemical cycling in the aquifer sediment. Community proteomics confirmed these activities. The eight most abundant organisms belong to novel lineages, and two represent phyla with no previously sequenced genome. Four organisms are predicted to fix carbon via the C alvin– B enson– B assham, W ood– L jungdahl or 3‐hydroxyproprionate/4‐hydroxybutarate pathways. The profiled organisms are involved in the network of denitrification, dissimilatory nitrate reduction to ammonia, ammonia oxidation and sulfate reduction/oxidation, and require substrates supplied by other community members. An ammonium‐oxidizing T haumarchaeote is the most abundant community member, despite low ammonium concentrations in the groundwater. This organism likely benefits from two other relatively abundant organisms capable of producing ammonium from nitrate, which is abundant in the groundwater. Overall, dominant members of the microbial community are interconnected through exchange of geochemical resources.

Lightning fatality risk map of the contiguous United States - William P. Roeder; Benjamin H. Cummins; Kenneth L. Cummins; Ronald L. Holle; Walker S. Ashley (Natural Hazards, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - C. William Yeung; Kenneth Lee; Susan Cobanli; Tom King; Jay Bugden; Lyle G. Whyte; Charles W. Greer (Environmental Science and Pollution Research, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Publishing and sharing multi-dimensional image data with OMERO - Jean-Marie Burel; Sébastien Besson; Colin Blackburn; Mark Carroll; Richard K. Ferguson; Helen Flynn; Kenneth Gillen; Roger Leigh; Simon Li; Dominik Lindner; Melissa Linkert; William J. Moore; et al. (Mammalian Genome, 2015)

Ascent and emplacement dynamics of obsidian lavas inferred from microlite textures - Kenneth S. Befus; Michael Manga; James E. Gardner; Matthew Williams (Bulletin of Volcanology, 2015)

Spatial patterns and predictors of trophic control in marine ecosystems - Daniel G. Boyce; Kenneth T. Frank; Boris Worm; William C. Leggett (Ecology Letters, 2015)
A key question in ecology is under which conditions ecosystem structure tends to be controlled by resource availability vs. consumer pressure. Several hypotheses derived from theory, experiments and observational field studies have been advanced, yet a unified explanation remains elusive. Here, we identify common predictors of trophic control in a synthetic analysis of 52 observational field studies conducted within marine ecosystems across the Northern Hemisphere and published between 1951 and 2014. Spatial regression analysis of 45 candidate variables revealed temperature to be the dominant predictor, with unimodal effects on trophic control operating both directly ( r 2 = 0.32; P

Melatonin administration alters nicotine preference consumption via signaling through high-affinity melatonin receptors - William J. Horton; Hannah J. Gissel; Jennifer E. Saboy; Kenneth P. Wright; Jerry A. Stitzel (Psychopharmacology, 2015)

From mice to elephants: overturning the ‘one size fits all’ paradigm in marine plankton food chains - Daniel G. Boyce; Kenneth T. Frank; William C. Leggett (Ecology Letters, 2015)
It is widely believed that consumer control is a weak regulator of marine phytoplankton communities. It remains unclear, however, why this should be the case when marine consumers routinely regulate their prey at higher trophic levels. One possibility is that the weak consumer control of phytoplankton communities results from the inability of field researchers to effectively account for consumer–prey trophic relationships operating at the scale of the plankton. We explored this issue by reviewing studies of trophic control in marine plankton. Experimental studies indicate that size is a critical determinant of feeding relationships among plankton. In sharp contrast, of the 51 field studies reviewed, 78% did not distinguish among the sizes or species of phytoplankton and their consumers, but instead assumed a general bulk phytoplankton–zooplankton trophic connection. Such an approach neglects the possibility that several trophic connections may separate the smallest phytoplankton (0.2 μm) from the larger zooplankton (~ 1000 μm), a remarkable size differential exceeding that between a mouse (~10 cm) and an elephant (~2500 cm). The size‐based approach we propose integrates theory, experiments and field observations and has the potential to greatly enhance our understanding of the causes and consequences of recently documented restructuring of plankton communities.

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

The complete genome sequence for putative H 2 ‐ and S ‐oxidizer C andidatus Sulfuricurvum sp., assembled de novo from an aquifer‐derived metagenome - Kim M. Handley; Daniela Bartels; Edward J. O'Loughlin; Kenneth H. Williams; William L. Trimble; Kelly Skinner; Jack A. Gilbert; Narayan Desai; Elizabeth M. Glass; Tobias Paczian; Andreas Wilke; Dionysios Antonopoulos; et al. (Environmental Microbiology, 2014)
Summary We reconstructed the complete 2.4 Mb‐long genome of a previously uncultivated epsilonproteobacterium, C andidatus Sulfuricurvum sp. RIFRC ‐1, via assembly of short‐read shotgun metagenomic data using a complexity reduction approach. Genome‐based comparisons indicate the bacterium is a novel species within the S ulfuricurvum genus, which contains one cultivated representative, S . kujiense . Divergence between the species appears due in part to extensive genomic rearrangements, gene loss and chromosomal versus plasmid encoding of certain (respiratory) genes by RIFRC ‐1. Deoxyribonucleic acid for the genome was obtained from terrestrial aquifer sediment, in which RIFRC ‐1 comprised ∼ 47% of the bacterial community. Genomic evidence suggests RIFRC ‐1 is a chemolithoautotrophic diazotroph capable of deriving energy for growth by microaerobic or nitrate‐/nitric oxide‐dependent oxidation of S 0 , sulfide or sulfite or H 2 oxidation. Carbon may be fixed via the reductive tricarboxylic acid cycle. Consistent with these physiological attributes, the local aquifer was microoxic with small concentrations of available nitrate, small but elevated concentrations of reduced sulfur and NH 4 + / NH 3 ‐limited. Additionally, various mechanisms for heavy metal and metalloid tolerance and virulence point to a lifestyle well‐adapted for metal(loid)‐rich environments and a shared evolutionary past with pathogenic E psilonproteobacteria . Results expand upon recent findings highlighting the potential importance of sulfur and hydrogen metabolism in the terrestrial subsurface.

Establishment and Short-term Productivity of Annual and Perennial Bioenergy Crops Across a Landscape Gradient - Danielle M. Wilson; Emily A. Heaton; Lisa A. Schulte; Theodore P. Gunther; Monika E. Shea; Richard B. Hall; William Landon Headlee; Kenneth J. Moore; Nicholas N. Boersma (BioEnergy Research, 2014)

Vaccine immunotherapy for prostate cancer: from mice to men - David M. Lubaroff; Daniel Vaena; James A. Brown; Pamela Zehr; Karen C. Griffith; Erica Brown; Julie Eastman; Kenneth Nepple; Ambika Kattula; Richard D. Williams (Immunologic Research, 2014)

Development of microsatellite loci for the western slimy salamander (Plethodon albagula) using 454 sequencing - Brett N. Spatola; William E. Peterman; Nathan T. Stephens; Grant M. Connette; Donald B. Shepard; Kenneth H. Kozak; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics Resources, 2013)

Setting the record straight on drivers of changing ecosystem states - Kenneth T. Frank; Brian Petrie; Jonathan A.D. Fisher; William C. Leggett (Fisheries Oceanography, 2013)
This short communication is a response to the critique by Greene (2012), who puts forward the argument that the dynamics of northwest A tlantic continental shelf ecosystems are strongly influenced by changes in A rctic climate, as indexed by surface salinity. The argument, in its essence, discounts any indirect effects from over‐exploitation of top predators on lower trophic levels in northwest A tlantic ecosystems. Frank et al . ( Science 308 , 2005, 1621; Nature 477 , 2011, 86) reported the existence of cascading trophic interactions with particular emphasis on the eastern S cotian S helf. Greene argues that the events occurring in the G ulf of M aine/ G eorges B ank region are representative of all N orthwest A tlantic shelf systems, despite previous research (Frank et al. Trends Ecol. Evol . 22 , 2007, 236; Petrie et al. Fish. Oceanogr . 18 , 2009, 83) that has shown a differential pattern of forcing ranging from top‐down in species‐poor, cold water systems to bottom‐up in warmer, more species‐rich systems, including G eorges B ank.

In Vivo Quantification of Active Decitabine-Triphosphate Metabolite: A Novel Pharmacoanalytical Endpoint for Optimization of Hypomethylating Therapy in Acute Myeloid Leukemia - Hongyan Wang; Ping Chen; Jiang Wang; Ramasamy Santhanam; Josephine Aimiuwu; U. V. Vijaya Saradhi; Zhongfa Liu; Sebastian Schwind; Alice Mims; John C. Byrd; Michael R. Grever; Miguel A. Villalona-Calero; et al. (The AAPS Journal, 2013)

Effects of Three Years of Regrowth Inhibition on the Resilience of a Clear-cut Northern Hardwood Forest - William A. Reiners; Kenneth L. Driese; Timothy J. Fahey; Kenneth G. Gerow (Ecosystems, 2012)

Estimated effects of climate change on flood vulnerability of U.S. bridges - Len Wright; Paul Chinowsky; Kenneth Strzepek; Russell Jones; Richard Streeter; Joel B. Smith; Jean-Marc Mayotte; Anthony Powell; Lesley Jantarasami; William Perkins (Mitigation and Adaptation Strategies for Global Change, 2012)

Outcomes of a systems-level intervention offering breast cancer risk assessments to low-income underserved women - Darren Mays; McKane E. Sharff; Tiffani A. DeMarco; Bernice Williams; Beth Beck; Vanessa B. Sheppard; Beth N. Peshkin; Jennifer Eng-Wong; Kenneth P. Tercyak (Familial Cancer, 2012)

Simulation of the intraseasonal variability over the Eastern Pacific ITCZ in climate models - Xianan Jiang; Duane E. Waliser; Daehyun Kim; Ming Zhao; Kenneth R. Sperber; William F. Stern; Siegfried D. Schubert; Guang J. Zhang; Wanqiu Wang; Marat Khairoutdinov; Richard B. Neale; Myong-In Lee (Climate Dynamics, 2012)

Uranium reduction and microbial community development in response to stimulation with different electron donors - Melissa Barlett; Hee Sun Moon; Aaron A. Peacock; David B. Hedrick; Kenneth H. Williams; Philip E. Long; Derek Lovley; Peter R. Jaffe (Biodegradation, 2012)

Monocyte Mobilization, Activation Markers, and Unique Macrophage Populations in the Brain: Observations from SIV Infected Monkeys Are Informative with Regard to Pathogenic Mechanisms of HIV Infection in Humans - Kenneth Williams; Tricia H. Burdo (Journal of Neuroimmune Pharmacology, 2012)

Methods for Studying the Ecological Physiology of Feeding in Free-Ranging Howlers (Alouatta palliata) at La Pacifica, Costa Rica - Christopher J. Vinyard; Kenneth E. Glander; Mark F. Teaford; Cynthia L. Thompson; Max Deffenbaugh; Susan H. Williams (International Journal of Primatology, 2012)

A global view of the OCA2-HERC2 region and pigmentation - Michael P. Donnelly; Peristera Paschou; Elena Grigorenko; David Gurwitz; Csaba Barta; Ru-Band Lu; Olga V. Zhukova; Jong-Jin Kim; Marcello Siniscalco; Maria New; Hui Li; Sylvester L. B. Kajuna; et al. (Human Genetics, 2012)

Heat tolerance, temperature acclimation, acute oxidative damage and canalization of haemoglobin expression in Daphnia - Patricia J. Williams; Kenneth B. Dick; Lev Y. Yampolsky (Evolutionary Ecology, 2012)

Neuropsychopharmacology and Neurogenetic Aspects of Executive Functioning: Should Reward Gene Polymorphisms Constitute a Diagnostic Tool to Identify Individuals at Risk for Impaired Judgment? - Abdalla Bowirrat; Thomas J. H. Chen; Marlene Oscar-Berman; Margaret Madigan; Amanda LH Chen; John A. Bailey; Eric R. Braverman; Mallory Kerner; John Giordano; Siobhan Morse; B. William Downs; Roger L. Waite; et al. (Molecular Neurobiology, 2012)

Hydrothermal Discharge During Submarine Eruptions: The Importance of Detection, Response, and New Technology - Edward Baker; William Chadwick; James Cowen; Robert Dziak; Kenneth Rubin; Daniel Fornari (Oceanography, 2012)

The East Pacific Rise Between 9°N and 10°N: Twenty-Five Years of Integrated, Multidisciplinary Oceanic Spreading Center Studies - Daniel Fornari; Karen Von Damm; Julia Bryce; James Cowen; Vicki Ferrini; Allison Fundis; Marvin Lilley; George Luther; Lauren Mullineaux; Michael Perfit; M. Florencia Meana-Prado; Kenneth Rubin; et al. (Oceanography, 2012)

Volcanic Eruptions in the Deep Sea - Kenneth Rubin; S. Adam Soule; William Chadwick; Daniel Fornari; David Clague; Robert Embley; Edward Baker; Michael Perfit; David Caress; Robert Dziak (Oceanography, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Can the Chronic Administration of the Combination of Buprenorphine and Naloxone Block Dopaminergic Activity Causing Anti-reward and Relapse Potential? - Kenneth Blum; Thomas J. H. Chen; John Bailey; Abdalla Bowirrat; John Femino; Amanda L. C. Chen; Thomas Simpatico; Siobhan Morse; John Giordano; Uma Damle; Mallory Kerner; Eric R. Braverman; et al. (Molecular Neurobiology, 2011)

Soil Carbon and Nitrogen Storage in Upper Montane Riparian Meadows - Jay B. Norton; Laura J. Jungst; Urszula Norton; Hayley R. Olsen; Kenneth W. Tate; William R. Horwath (Ecosystems, 2011)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Yellowstone Lake: high‐energy geochemistry and rich bacterial diversity - Scott Clingenpeel; Richard E. Macur; Jinjun Kan; William P. Inskeep; Dave Lovalvo; John Varley; Eric Mathur; Kenneth Nealson; Yuri Gorby; Hongchen Jiang; Toben LaFracois; Timothy R. McDermott (Environmental Microbiology, 2011)
Summary Yellowstone Lake is central to the balanced functioning of the Yellowstone ecosystem, yet little is known about the microbial component of its food chain. A remotely operated vehicle provided video documentation ( http://www.tbi.montana.edu/media/videos/ ) and allowed sampling of dilute surface zone waters and enriched lake floor hydrothermal vent fluids. Vent emissions contained substantial H 2 S, CH 4 , CO 2 and H 2 , although CH 4 and H 2 levels were also significant throughout the lake. Pyrosequencing and near full‐length sequencing of Bacteria 16S rRNA gene diversity associated with two vents and two surface water environments demonstrated that this lake contains significant bacterial diversity. Biomass was size‐fractionated by sequentially filtering through 20‐µm‐, 3.0‐µm‐, 0.8‐µm‐ and 0.1‐µm‐pore‐size filters, with the > 0.1 to Acidobacteria , Actinobacteria , Bacteroidetes , α‐ and β‐ Proteobacteria and Cyanobacteria , with 21 other phyla represented at varying levels. Surface waters were dominated by two phylotypes: the Actinobacteria freshwater ac I group and an α‐ Proteobacteria clade tightly linked with freshwater SAR11‐like organisms. We also obtained evidence of novel thermophiles and recovered Prochlorococcus phylotypes (97–100% identity) in one near surface photic zone region of the lake. The combined geochemical and microbial analyses suggest that the foundation of this lake's food chain is not simple. Phototrophy presumably is an important driver of primary productivity in photic zone waters; however, chemosynthetic hydrogenotrophy and methanotrophy are likely important components of the lake's food chain.

Lack of effect of hydrochlorothiazide and low-dose aspirin on the renal clearance of urate and oxypurinol after a single dose of allopurinol in normal volunteers - Daniel Y. Ng; Sophie L. Stocker; Garry G. Graham; Kenneth M. Williams; Richard O. Day (European Journal of Clinical Pharmacology, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Collapsin Response Mediator Protein-2: An Emerging Pathologic Feature and Therapeutic Target for Neurodisease Indications - Kenneth Hensley; Kalina Venkova; Alexandar Christov; William Gunning; Joshua Park (Molecular Neurobiology, 2011)

Alterations in brain metabolism during the first year of HIV infection - Margaret R. Lentz; Woong-Ki Kim; Hyun Kim; Caroline Soulas; Vallent Lee; Nagagopal Venna; Elkan F. Halpern; Eric S. Rosenberg; Kenneth Williams; R. G. González (Journal of NeuroVirology, 2011)

Assessment of potential pharmacokinetic interactions of ezetimibe/simvastatin and extended-release niacin tablets in healthy subjects - Teddy Kosoglou; Yali Zhu; Paul Statkevich; Ilias Triantafyllou; William Taggart; Fengjuan Xuan; Kenneth T. Kim; David L. Cutler (European Journal of Clinical Pharmacology, 2011)

Spatial, seasonal, and ontogenetic variations in the significance of detrital pathways and terrestrial carbon for a benthic shark, Chiloscyllium plagiosum (Hemiscylliidae), in a tropical estuary - Tak-Cheung Wai; Kenneth M. Y. Leung; Shadow Y. T. Sin; Andy Cornish; David Dudgeon; Gray A. Williams (Limnology and Oceanography, 2011)
Using a combination of stable isotope analyses (SIA), fatty acid profiling (FAP), and FA‐specific SIA, we investigated the relative importance of terrestrial‐ and marine‐derived carbon, and spatial (inshore vs. offshore), seasonal (wet vs. dry season), and ontogenetic variations, in the relative contribution of detrital pathways to the white‐spotted bamboo shark, Chiloscyllium plagiosum in the Pearl River estuary. SIA and FAP suggested the sharks acquired carbon from both marine‐ and terrestrial‐derived detritus via consumption of polychaetes and small crustaceans, with carbon from terrestrial sources being more important to juveniles (25–50 cm long) at inshore locations. Juveniles generally had significantly higher levels of diatom FA, bacterial FA, and long‐chain‐carbon–saturated FA biomarkers than adults (> 65 cm), especially during the wet season, suggesting that they relied on primary consumers which assimilated a mixture of autotrophic and detrital carbon sources. Levels of zooplankton and animal‐derived FA biomarkers generally increased with shark size, indicating an ontogenetic dietary shift. Utilizing the results of FA‐specific SIA (i.e., δ 13 C values of individual bacterial FA of detritus) from four sources (i.e., terrestrial plant litter, macroalgae, phytoplankton, and sediments), Bayesian mixing models revealed juveniles in the inner estuary assimilated significantly higher amounts of terrestrial carbon (37–45%) than adults (22–37%) or sharks in the outer estuary (1–36%). The combined use of multiple dietary tracers effectively revealed the interaction of various detrital pathways to marine predators in the Pearl River estuary, and highlighted the importance of terrestrial–marine linkages for interpretation of energy flow in coastal ecosystems.

A climatological analysis of heatbursts in Oklahoma (1994–2009) - Renee A. McPherson; Justin D. Lane; Kenneth C. Crawford; William G. McPherson (International Journal of Climatology, 2011)
Heatbursts are characterized by a sudden and highly localized increase in air temperature, a simultaneous decrease in relative humidity and dewpoint temperature, and strong gusty winds, typically associated with decaying thunderstorms. The small spatial extent and short duration of most heatbursts makes detailed study of these events difficult using the standard federal observation network (e.g. hourly observations) established in most countries. Thus, many discussions of heatbursts note that they are ‘rare’ phenomena. However, observations from the Oklahoma Mesonet indicate that although heatbursts are meso‐alpha scale phenomena, they are not rare. Using multi‐criteria analysis, 207 heatburst events of various magnitudes, areal coverage and duration were identified between 1994 and 2009 across Oklahoma. Significantly more heatbursts were detected in the western two‐thirds of the state as compared to the eastern third. Heatbursts were primarily nocturnal events, with 70% of heatburst events initiated between 0000 and 0800 UTC (i.e. between 6 p.m. and 2 a.m. Central Standard Time). With 62 of the 207 events, June was the most active month for heatbursts. At the other extreme, no heatbursts were detected during February and November, and only one was observed during January and December. Almost all of the heatbursts occurred underneath or adjacent to weak radar echoes at the time of the event. Four basic radar patterns were associated with the events: (1) radar echoes associated with rapidly weakening convection, (2) weak reflectivity not produced by or associated with deep moist convection, (3) weak radar echoes to the rear of a dissipating mesoscale convective system (MCS) and (4) weak reflectivity along the periphery of intense convection that did not appear to be weakening. Copyright © 2010 Royal Meteorological Society

Medical Students Educate Teens About Skin Cancer: What Have We Learned? - Jeanette M. Kamell; William Rietkerk; Ken Lam; Jason M. Phillips; Jashin J. Wu; Jerry L. McCullough; Kenneth G. Linden; Kathryn Osann (Journal of Cancer Education, 2011)

Modeling misidentification errors that result from use of genetic tags in capture–recapture studies - Jun Yoshizaki; Cavell Brownie; Kenneth H. Pollock; William A. Link (Environmental and Ecological Statistics, 2011)

Identification of trace-amine-associated receptors (TAAR) in the rat aorta and their role in vasoconstriction by β-phenylethylamine - Martina Fehler; Kenneth J. Broadley; William R. Ford; Emma J. Kidd (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Long-Term Trends in Submersed Aquatic Vegetation (SAV) in Chesapeake Bay, USA, Related to Water Quality - Robert J. Orth; Michael R. Williams; Scott R. Marion; David J. Wilcox; Tim J. B. Carruthers; Kenneth A. Moore; W. Michael Kemp; William C. Dennison; Nancy Rybicki; Peter Bergstrom; Richard A. Batiuk (Estuaries and Coasts, 2010)

Effects of Forage Quality and Cell Wall Constituents of Bermuda Grass on Biochemical Conversion to Ethanol - William F. Anderson; Bruce S. Dien; Hans-Joachim G. Jung; Kenneth P. Vogel; Paul J. Weimer (BioEnergy Research, 2010)

Breaking Bergmann's rule: truncation of Northwest Atlantic marine fish body sizes - Jonathan A. D. Fisher; Kenneth T. Frank; William C. Leggett (Ecology, 2010)
A strictly species‐centric view of human impacts on ecological communities may conceal important trait changes key to ecosystem functioning and stability. Analyses of body size and community composition data for 326 Northwest Atlantic fish species sampled across >900 000 km 2 over three decades revealed a rapid and widespread reduction of body sizes driven by declines within species and changes in relative abundances. The changes were unrelated to species richness but of sufficient magnitude to eliminate biogeographic scale gradients of increasing body size with latitude commonly characterized as Bergmann's rule. These changes have persisted despite reduced potential for intraspecific competition and favorable bottom water temperatures, both of which should lead to increased growth rates. The aggregate body sizes in these Northwest Atlantic fish communities may now represent a mismatch between the environmental variability characteristic of the Northwest Atlantic and the historical body size, life history traits, and productivity of species across this region. We discuss how these changes may jeopardize the potential for recovery of these important temperate/subarctic ecosystems.

Bromide and N-acetyl-S-(n-propyl)-l-cysteine in urine from workers exposed to 1-bromopropane solvents from vapor degreasing or adhesive manufacturing - Kevin William Hanley; Martin R. Petersen; Kenneth L. Cheever; Lian Luo (International Archives of Occupational and Environmental Health, 2010)

Following the chain to elusive anglers - Shane P. Griffiths; Kenneth H. Pollock; Jeremy M. Lyle; Julian G. Pepperell; Mark L. Tonks; William Sawynok (Fish and Fisheries, 2010)
Obtaining reliable estimates of important parameters from recreational fisheries is problematic but critical for stock assessment and effective resource management. Sampling methodologies based on traditional design‐based sampling theory, is inadequate in obtaining representative catch and effort data, social or demographical characterization, or fisher behaviour from small hard‐to‐reach components within recreational fisheries (e.g. specialized sport fisheries) that may account for the majority of the catch for some species. A model‐based approach to sampling is necessary. Researchers in other disciplines including epidemiology and social sciences routinely survey rare or ‘hidden’ populations within the general community by penetration of social networks rather than by interception of individuals. We encourage fisheries researchers to rethink survey designs and consider the social elements of recreational fishing. Employing chain‐referral methods, such as respondent‐driven sampling (RDS), may be a statistically robust and cost‐effective option for sampling elusive sub‐elements within recreational fisheries. Chain‐referral sampling methodology is outlined and an example of a complemented ‘RDS‐recapture’ survey design is introduced as a cost‐effective application to estimating total catch in recreational fisheries.

Historical and paleolimnological evidence for expansion of Lake Athabasca (Canada) during the Little Ice Age - R. Niloshini Sinnatamby; Yi Yi; Michael A. Sokal; Kenneth P. Clogg-Wright; Taro Asada; Sheila R. Vardy; Tammy L. Karst-Riddoch; William M. Last; John W. Johnston; Roland I. Hall; Brent B. Wolfe; Thomas W. D. Edwards (Journal of Paleolimnology, 2010)

Mercury in South Carolina Fishes, USA - James B. Glover; Marisa E. Domino; Kenneth C. Altman; James W. Dillman; William S. Castleberry; Jeannie P. Eidson; Micheal Mattocks (Ecotoxicology, 2010)

SNPs for a universal individual identification panel - Andrew J. Pakstis; William C. Speed; Rixun Fang; Fiona C. L. Hyland; Manohar R. Furtado; Judith R. Kidd; Kenneth K. Kidd (Human Genetics, 2010)

Dynamic macroecology on ecological time‐scales - Jonathan A. D. Fisher; Kenneth T. Frank; William C. Leggett (Global Ecology and Biogeography, 2010)
Aim The discipline of macroecology is increasingly being regarded as an effective vehicle for the evaluation of recent population‐ to ecosystem‐level responses to widespread human and environmental influences. However, due to the prevalent use of time‐averaged and cumulative data in macroecological analyses, the majority of the patterns that emerge from research in this field can be regarded as static. Here we review the application of dynamic macroecological analyses to changes in relationships between macroecological variables on seasonal to decadal scales. We illustrate the strength of this perspective for documenting changing patterns and testing hypotheses related to these dynamics on ecological time‐scales. Location Studies were compiled and reviewed from terrestrial and aquatic ecosystems. Methods We review examples of temporal changes in macroecological patterns driven by recent anthropogenic influences and environmental change. Results The dynamic nature of macroecological patterns on ecological time‐scales has been revealed in recent years across a wide range of ecosystems, largely through the development, maintenance and analysis of biotic and environmental monitoring time series. The resultant analyses complement examinations of dynamics over evolutionary time and have similarly revealed that static portrayals can conceal important temporal dynamics that underlie the patterns of interest. As a consequence, static depictions, resting as they do on comparative analyses in which the validity of space‐for‐time substitutions is assumed, may be of limited use for testing hypotheses related to the mechanisms underlying the patterns revealed and, by extension, the development of reliable predictions of future states. Main conclusions Recent dynamic macroecological analyses have demonstrated the utility of combined spatial and temporal replication, and have contributed to hypothesis testing related to the mechanistic processes underlying changes in macroecological patterns on ecological time‐scales. We suggest four specific avenues of future research to further the development and application of temporal approaches on similar time‐scales within the field of macroecology.

Climate‐related, decadal‐scale assemblage changes of seagrass‐associated fishes in the northern Gulf of Mexico - F. JOEL FODRIE; KENNETH L. HECK; SEAN P. POWERS; WILLIAM M. GRAHAM; KELLY L. ROBINSON (Global Change Biology, 2010)
Global temperatures are rising, and are expected to produce a poleward shift in the distribution of many organisms. We quantified changes in fish assemblages within seagrass meadows of the northern Gulf of Mexico (GOM) between the 1970s and 2006–2007, and observed changes consistent with this forecast. During 2006–2007 we sampled seagrass meadows using the same gears and methods previously employed by R. J. Livingston in coastal waters of northwest Florida throughout the 1970s. Comparisons between datasets revealed numerous additions to the fish fauna during 2006–2007 that were completely absent in the 1970s, including: Lutjanus synagris (lane snapper), Epinephelus morio (red grouper), Chaetodon ocellatus (spotfin butterflyfish), Mycteroperca sp (grouper, non gag), Centropristis philadelphica (rock sea bass), Fistularia tabacaria (bluespotted cornetfish), Ocyurus chrysurus (yellowtail snapper), Thalassoma bifasciatum (bluehead wrasse), Abudefduf saxatilis (sergeant major), Acanthuridae spp. (surgeonfishes) and Sparisoma viride (stoplight parrotfish). Several other species showed large increases in abundance during the interval between 1979 and 2006, including Mycteroperca microlepis (gag grouper, up ∼200 ×), Lutjanus griseus (gray snapper, up ∼105 ×), and Nicholsina usta (emerald parrotfish, up ∼22 ×). All of these are tropical or subtropical species that now make up a greater percentage of seagrass‐associated fish assemblages in the northern GOM than in the past. Additionally, we observed regional increases in air and sea surface temperatures (> 3 °C) during the ∼30 years that separate Livingston's samples and ours that correlate with northern shifts in the distribution of warm‐water fishes. Documenting these range shifts is a critical first step in investigating the consequences of global warming for endemic marine communities and fishery production in the northern GOM.

Seasonal foraging and piscivory by sympatric wild and hatchery-reared steelhead from an integrated hatchery program - William G. Simpson; Benjamen M. Kennedy; Kenneth G. Ostrand (Environmental Biology of Fishes, 2009)

Lakes and reservoirs as regulators of carbon cycling and climate - Lars J. Tranvik; John A. Downing; James B. Cotner; Steven A. Loiselle; Robert G. Striegl; Thomas J. Ballatore; Peter Dillon; Kerri Finlay; Kenneth Fortino; Lesley B. Knoll; Pirkko L. Kortelainen; Tiit Kutser; et al. (Limnology and Oceanography, 2009)
We explore the role of lakes in carbon cycling and global climate, examine the mechanisms influencing carbon pools and transformations in lakes, and discuss how the metabolism of carbon in the inland waters is likely to change in response to climate. Furthermore, we project changes as global climate change in the abundance and spatial distribution of lakes in the biosphere, and we revise the estimate for the global extent of carbon transformation in inland waters. This synthesis demonstrates that the global annual emissions of carbon dioxide from inland waters to the atmosphere are similar in magnitude to the carbon dioxide uptake by the oceans and that the global burial of organic carbon in inland water sediments exceeds organic carbon sequestration on the ocean floor. The role of inland waters in global carbon cycling and climate forcing may be changed by human activities, including construction of impoundments, which accumulate large amounts of carbon in sediments and emit large amounts of methane to the atmosphere. Methane emissions are also expected from lakes on melting permafrost. The synthesis presented here indicates that (1) inland waters constitute a significant component of the global carbon cycle, (2) their contribution to this cycle has significantly changed as a result of human activities, and (3) they will continue to change in response to future climate change causing decreased as well as increased abundance of lakes as well as increases in the number of aquatic impoundments.

Observing Biogeochemical Cycles at Global Scales with Profiling Floats and Gliders: Prospects for a Global Array - Kenneth Johnson; William Berelson; Emmanuel Boss; Zanna Chase; Hervé Claustre; Steven Emerson; Nicolas Gruber; Arne Körtzinger; Mary Jane Perry; Stephen Riser (Oceanography, 2009)

Understanding Causes and Impacts of the Dinoflagellate, Cochlodinium polykrikoides, Blooms in the Chesapeake Bay - Margaret R. Mulholland; Ryan E. Morse; George E. Boneillo; Peter W. Bernhardt; Katherine C. Filippino; Leo A. Procise; Jose L. Blanco-Garcia; Harold G. Marshall; Todd A. Egerton; William S. Hunley; Kenneth A. Moore; Dianna L. Berry; et al. (Estuaries and Coasts, 2009)

A Literal Use of “Forest Health” Safeguards against Misuse and Misapplication - Kenneth F. Raffa; Brian Aukema; Barbara J. Bentz; Allan Carroll; Nadir Erbilgin; Daniel A. Herms; Jeffrey A. Hicke; Richard W. Hofstetter; Steven Katovich; B. Staffan Lindgren; Jesse Logan; William Mattson; et al. (Journal of Forestry, 2009)

A LC-MS/MS Method for the Analysis of Intracellular Nucleoside Triphosphate Levels - Ping Chen; Zhongfa Liu; Shujun Liu; Zhiliang Xie; Josephine Aimiuwu; Jiuxia Pang; Rebecca Klisovic; William Blum; Michael R. Grever; Guido Marcucci; Kenneth K. Chan (Pharmaceutical Research, 2009)

Structure and stability in exploited marine fish communities: quantifying critical transitions - BRIAN PETRIE; KENNETH T. FRANK; NANCY L. SHACKELL; WILLIAM C. LEGGETT (Fisheries Oceanography, 2009)
Correlations between time series of the abundance of predator and prey fish species in heavily exploited western North Atlantic marine fisheries vary temporally but are generally positive in southern, warmer waters and negative in northern, colder ones. The correlations provide an index of trophic structure and dynamics. We construct a framework to quantify critical thresholds between states in which the predator–prey correlations are positive or negative. We do so by developing a quantitative model of the distribution of the correlations between predator (15 species) and prey (8 species) functional groups based on the annual predator depletion rates and bottom temperatures (or alternatively species richness). The model accounts for 58% of the variance of the correlations with a root mean square error of 0.3. This index of trophic structure indicates that warmer, species‐rich, southern fish populations resist transformation from positive to negative predator–prey correlations at exploitation rates that can be double those in the colder, relatively species‐poor, northern areas. The model can be used to set limits for exploitation rates that preserve the functional relationships between predator–prey groups in emerging fisheries, and to assess the potential for and measures required to achieve recovery of degraded fish communities.

Explaining Clustered Ventilation Defects Via a Minimal Number of Airway Closure Locations - William Mullally; Margrit Betke; Mitchell Albert; Kenneth Lutchen (Annals of Biomedical Engineering, 2009)

Activation of β-adrenoceptors mimics preconditioning of rat-isolated atria and ventricles against ischaemic contractile dysfunction - Peter E. Penson; William R. Ford; Emma J. Kidd; Kenneth J. Broadley (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Lemur Diversity in Madagascar - Russell A. Mittermeier; Jörg U. Ganzhorn; William R. Konstant; Kenneth Glander; Ian Tattersall; Colin P. Groves; Anthony B. Rylands; Andreas Hapke; Jonah Ratsimbazafy; Mireya I. Mayor; Edward E. Louis; Yves Rumpler; et al. (International Journal of Primatology, 2008)

Telemetry System for Assessing Jaw-Muscle Function in Free-ranging Primates - Susan H. Williams; Christopher J. Vinyard; Kenneth E. Glander; Max Deffenbaugh; Mark F. Teaford; Cynthia L. Thompson (International Journal of Primatology, 2008)

Gestalt-binding of tropomyosin to actin filaments - Kenneth C. Holmes; William Lehman (Journal of Muscle Research and Cell Motility, 2008)

Trophic Transfers from Seagrass Meadows Subsidize Diverse Marine and Terrestrial Consumers - Kenneth L. Heck; Tim J. B. Carruthers; Carlos M. Duarte; A. Randall Hughes; Gary Kendrick; Robert J. Orth; Susan W. Williams (Ecosystems, 2008)

Temporal dynamics within a contemporary latitudinal diversity gradient - Jonathan A. D. Fisher; Kenneth T. Frank; Brian Petrie; William C. Leggett; Nancy L. Shackell (Ecology Letters, 2008)
Poleward declines in species diversity [latitudinal diversity gradients (LDG)] remain among the oldest and most widespread of macroecological patterns. However, their contemporary dynamics remain largely unexplored even though changing ecological conditions, including global change, may modify LDG and their respective ecosystems. Here, we examine temporal variation within a temperate Northwest Atlantic LDG using 31 years of annual fisheries‐independent surveys and explore its dynamics in relation to a dominant climate signal [the wintertime North Atlantic Oscillation (NAO)] that varies interannually and alters the latitudinal gradient of Northwest Atlantic continental shelf bottom water temperatures. We found that the slopes of the annual LDG vary dramatically due to changes in geographic distributions of 100+ species, variations that are concealed within the cumulative, static LDG. These changes are strongly associated with changes in NAO sign and strength. This is the first illustration of temporal dynamics in a contemporary LDG and the first demonstration of the speed at which local environmental variations can alter an LDG. Our findings underscore the need to investigate factors that modify LDG separately from those that contribute to their origins.

The source and fate of organic matter and the significance of detrital pathways in a tropical coastal ecosystem - Tak-Cheung Wai; Jasmine S. S. Ng; Kenneth M. Y. Leung; David Dudgeon; Gray A. Williams (Limnology and Oceanography, 2008)
Stable isotope analysis (SIA) and fatty acid profiling were used to elucidate the supply and fate of energy in a tropical coastal ecosystem in Hong Kong, southern China. To investigate seasonal changes in source supply on the diets of different trophic guilds, measurements were taken in three rocky bays before and after the onset of the summer monsoon, when supply of both marine macroalgal and streamborne terrestrial detritus increases. Particulate organic matter, comprising a mixture of marine and terrestrial sources, was the ultimate food source (>60%) for suspension feeders, which were the major prey items of a predatory gastropod ( Thais ). Increased levels of bacterial fatty acid biomarkers (BaFA) were recorded after the onset of the summer monsoon, indicating amplified dependence on detrital materials in both primary and secondary consumers. The considerable increase in the detritus fraction of sedimentary organic matter at the onset of the summer monsoon was reflected by enhanced levels of BaFA, possibly due to the degeneration of macroalgae. Significant contributions of this marine algal detritus to deposit feeders ( Holothuria , 36%) and of terrestrial detritus to an echinoid grazer ( Salmacis , 14%) were revealed by SIA mixing models as well as elevated BaFA concentrations. These results indicate a higher dependence on heterotrophic food chains based on decomposing marine algae and terrestrial detritus after the onset of the summer monsoon. Such seasonal variation in the importance of detrital energy sources is, therefore, likely to be important to coastal ecosystem functioning in the monsoonal tropics.

The Collaborative Cross at Oak Ridge National Laboratory: developing a powerful resource for systems genetics - Elissa J. Chesler; Darla R. Miller; Lisa R. Branstetter; Leslie D. Galloway; Barbara L. Jackson; Vivek M. Philip; Brynn H. Voy; Cymbeline T. Culiat; David W. Threadgill; Robert W. Williams; Gary A. Churchill; Dabney K. Johnson; et al. (Mammalian Genome, 2008)

Adverse effects from environmental mercury loads on breeding common loons - David C. Evers; Lucas J. Savoy; Christopher R. DeSorbo; David E. Yates; William Hanson; Kate M. Taylor; Lori S. Siegel; John H. Cooley; Michael S. Bank; Andrew Major; Kenneth Munney; Barry F. Mower; et al. (Ecotoxicology, 2008)

The effect of salinity on survival, bioenergetics and predation risk in the mud crabs Panopeus simpsoni and Eurypanopeus depressus - Yasoma D. Hulathduwa; William B. Stickle; Kenneth M. Brown (Marine Biology, 2007)

Electrical resistivity imaging of conductive plume dilution in fractured rock - Robin E. Nimmer; James L. Osiensky; Andrew M. Binley; Kenneth F. Sprenke; Barbara C. Williams (Hydrogeology Journal, 2007)

Comparative Phloem Chemistry of Manchurian (Fraxinus mandshurica) and Two North American Ash Species (Fraxinus americana and Fraxinus pennsylvanica) - Alieta Eyles; William Jones; Ken Riedl; Don Cipollini; Steven Schwartz; Kenneth Chan; Daniel A. Herms; Pierluigi Bonello (Journal of Chemical Ecology, 2007)

Candidate SNPs for a universal individual identification panel - Andrew J. Pakstis; William C. Speed; Judith R. Kidd; Kenneth K. Kidd (Human Genetics, 2007)

Purification and properties of glutathione reductase from liver of the anoxia-tolerant turtle, Trachemys scripta elegans - William. G. Willmore; Kenneth. B. Storey (Molecular and Cellular Biochemistry, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

The Use of Poly(Sodium N-Undecanoyl-l-Leucylvalinate), Poly(Sodium N-Undecanoyl-l-Leucinate) and Poly(Sodium N-Undecanoyl-l-Valinate) Surfactants as Chiral Selectors for Determination of Enantiomeric Composition of Samples by Multivariate Regression Modeling of Fluorescence Spectral Data - Sayo O. Fakayode; Alicia A. Williams; Marianna A. Busch; Kenneth W. Busch; Isiah M. Warner (Journal of Fluorescence, 2006)

A Specific Picomolar Hybridization-Based ELISA Assay for the Determination of Phosphorothioate Oligonucleotides in Plasma and Cellular Matrices - Xiaohui Wei; Guowei Dai; Guido Marcucci; Zhongfa Liu; Dale Hoyt; William Blum; Kenneth K. Chan (Pharmaceutical Research, 2006)

How replicable are mRNA expression QTL? - Jeremy L. Peirce; Hongqiang Li; Jintao Wang; Kenneth F. Manly; Robert J. Hitzemann; John K. Belknap; Glenn D. Rosen; Shirlean Goodwin; Thomas R. Sutter; Robert W. Williams; Lu Lu (Mammalian Genome, 2006)

Time-Dependent Instantaneous Mortality Rates from Multiple Tagging Experiments with Exact Times of Release and Recovery - George M. Leigh; William S. Hearn; Kenneth H. Pollock (Environmental and Ecological Statistics, 2006)

Formation of the Campbell-Red Lake gold deposit by H2O-poor, CO2-dominated fluids - Guoxiang Chi; Benoît Dubé; Kenneth Williamson; Anthony E. Williams-Jones (Mineralium Deposita, 2006)

Characterization of lymphocytic infiltrates in progressive multifocal leukoencephalopathy: Co-localization of CD8 + T cells with JCV-infected glial cells - Christian Wüthrich; Santosh Kesari; Woong-Ki Kim; Kenneth Williams; Rebecca Gelman; Derek Elmeric; Umberto De Girolami; Jeffrey T Joseph; Tessa Hedley-Whyte; Igor J Koralnik (Journal of NeuroVirology, 2006)

Genetic mapping of expressed sequences in onion and in silico comparisons with rice show scant colinearity - William J. Martin; John McCallum; Masayoshi Shigyo; Jernej Jakse; Joseph C. Kuhl; Naoko Yamane; Meeghan Pither-Joyce; Ali Fuat Gokce; Kenneth C. Sink; Christopher D. Town; Michael J. Havey (Molecular Genetics and Genomics, 2005)

Use of autosomal loci for clustering individuals and populations of East Asian origin - Jong-Jin Kim; Paul Verdu; Andrew J. Pakstis; William C. Speed; Judith R. Kidd; Kenneth K. Kidd (Human Genetics, 2005)

A 17 000‐year history of Andean climate and vegetation change from Laguna de Chochos, Peru - Mark B. Bush; Barbara C. S. Hansen; Donald T. Rodbell; Geoffrey O. Seltzer; Kenneth R. Young; Blanca León; Mark B. Abbott; Miles R. Silman; William D. Gosling (Journal of Quaternary Science, 2005)
The manifestation of major climatic events such as the timing of deglaciation and whether, or not, the Younger Dryas affected Andean systems has garnered considerable recent attention. Even the Holocene is rapidly emerging as a time of considerable interest in Neotropical palaeoclimatology and palaeoecology. The Holocene of the Neotropics is now revealed as a time of some temperature change with precipitation:evaporation ratios fluctuating markedly. Major changes in lake level, ice‐accumulation, and vegetation are indicative of changes both in precipitation and temperature regimes. Although global‐scale forcing mechanisms may underlie some of these changes, e.g. the precessional rhythm, other variability appears to be localised. In a record from near the upper forest limit of the eastern Peruvian Andes, pollen, charcoal, and sedimentary data suggest that the deglaciational period from ca. 17 000 to ca. 11 500 cal. yr BP was a period of rapid climatic oscillations, set against an overall trend of warming. A warm‐dry event is evident between ca. 9500 and ca. 7300 cal. yr BP, and comparisons with other regional archives suggest that it was regional in scale. A ca. 1500‐yr periodicity in the magnetic susceptibility data is evident between 12 000 and 6000 cal. yr BP, reaching a peak intensity during the dry event. A weaker oscillation with a 500–600‐yr periodicity is present throughout much of the Holocene. The uppermost sample of the pollen analysis reveals deforestation as modern human land use simplified the landscape. Copyright © 2005 John Wiley & Sons, Ltd.

Disruption of magnetic orientation in hatchling loggerhead sea turtles by pulsed magnetic fields - William P. Irwin; Kenneth J. Lohmann (Journal of Comparative Physiology A, 2005)

The role of monocytes and perivascular macrophages in HIV and SIV neuropathogenesis: Information from non-human primate models - Woong-Ki Kim; Xavier Alvarez; Kenneth Williams (Neurotoxicity Research, 2005)

Comparing Simulated and Measured Soil Organic Carbon Content of Clay Soils for Time Periods Up to 60 Years - Kenneth N. Potter; Steven R. Potter; Jay D. Atwood; Jimmy R. Williams (Environmental Management, 2004)

Chloride ligation in inorganic manganese model compounds relevant to Photosystem II studied using X-ray absorption spectroscopy - Shelly A. Pizarro; Hendrik Visser; Roehl M. Cinco; John H. Robblee; Samudranil Pal; Sumitra Mukhopadhyay; Henry J. Mok; Kenneth Sauer; Karl Wieghardt; William H. Armstrong; Vittal K. Yachandra (JBIC Journal of Biological Inorganic Chemistry, 2004)

Denitrification and soil characteristics of wetlands created on two mine soils in east Texas, USA - Daniel Johns; Hans Williams; Kenneth Farrish; Stephen Wagner (Wetlands, 2004)

Identification of T lymphocytes in simian immunodeficiency virus encephalitis: Distribution of CD8 + T cells in association with central nervous system vessels and virus - Woong-Ki Kim; Sarah Corey; Gillian Chesney; Heather Knight; Sherry Klumpp; Christian Wüthrich; Norman L Letvin; Igor J Koralnik; Andrew Lackner; Ronald S Veasey; Kenneth Williams (Journal of NeuroVirology, 2004)

Analysis of Anal Droplets of the Western Flower Thrips Frankliniella occidentalis - Kenneth M. MacDonald; James G. C. Hamilton; Robert Jacobson; William D. J. Kirk (Journal of Chemical Ecology, 2003)

A general model for tagging on multiple component fisheries: an integration of age-dependent reporting rates and mortality estimation - Kenneth H. Pollock; William S. Hearn; Thomas Polacheck (Environmental and Ecological Statistics, 2002)

Book reviews - C. Moran; Wayt Thomas; Marccus Alves; William R. Buck; Kenneth M. Cameron (Brittonia, 2001)

Deficit irrigation strategies using midday stem water potential in prune - Bruce D. Lampinen; Kenneth A. Shackel; Stephen M. Southwick; William H. Olson (Irrigation Science, 2001)

Ambient air levels of Aspergillus fumigatus and thermophilic actinomycetes in a residential neighborhood near a yard-waste composting facility - Gregg M. Recer; Marilyn L. Browne; Edward G. Horn; Kenneth M. Hill; William F. Boehler (Aerobiologia, 2001)

Dopamine transporter binding without cocaine-like behavioral effects: synthesis and evaluation of benztropine analogs alone and in combination with cocaine in rodents - Jonathan L. Katz; Gregory E. Agoston; Kenneth L. Alling; Richard H. Kline; Michael J. Forster; William L. Woolverton; Theresa A. Kopajtic; Amy H. Newman (Psychopharmacology, 2001)

Influence of stream size on ammonium and suspended particulate nitrogen processing - Wilfred M. Wollheim; Bruce J. Peterson; Linda A. Deegan; John E. Hobbie; Beth Hooker; William B. Bowden; Kenneth J. Edwardson; David B. Arscott; Anne E. Hershey; Jacques Finlay (Limnology and Oceanography, 2001)
We used 15 NH 4 tracer additions to determine travel distances of ammonium (NH4 ) and suspended particulate organic nitrogen (SPON) in six streams ranging from second to fifth order located within a single watershed on the North Slope of Alaska. Based on the distribution of 15 N stored in stream bottom compartments (primary producers or grazers), we estimated NH 4 travel lengths. We used a two‐compartment model to estimate the travel length of SPON based on the distribution of source 15 N on the stream bottom and SPO 15 N in the water column. Both NH 4 and SPON travel lengths (S w and S p , respectively) increased with discharge primarily due to changes in depth and velocity. Variation in the vertical mass transfer coefficient ( v f ) of both NH 4 and SPON did occur among the streams but was not related to stream size and was relatively small compared to the change in physical characteristics. Thus, in the Kuparuk watershed, physical gradients outweighed biological or chemical changes as controls on NH 4 and SPON travel length. The one exception was the Kuparuk fertilized reach, where phosphorus fertilization greatly increased biological activity and NH 4 processing compared to unaltered streams. Longitudinal gradients in major biological driving variables such as litter inputs, debris dams, and shading are absent in the Arctic, perhaps explaining the relatively uniform NH 4 ‐ v f . Watersheds in other biomes may show differing degrees of physical versus biological/chemical controls. A conceptual model is presented for comparing the relative strength of these controls among different watersheds. Strong relationships between discharge and travel length should greatly aid development of watershed models of nutrient dynamics.

Identification of novel Tapasin polymorphisms and linkage disequilibrium to MHC class I alleles - Anthony P. Williams; Steven Bevan; Mike Bunce; Richard Houlston; Kenneth I. Welsh; Tim Elliott (Immunogenetics, 2000)

Detection and Quantification of Spongospora subterranea f. sp. subterranea in Soils and on Tubers Using Specific PCR Primers - Kenneth S. Bell; Jane Roberts; Susan Verrall; Daniel W. Cullen; Naomi A. Williams; Julian G. Harrison; Ian K. Toth; David E.L. Cooke; James M. Duncan; Jamie R. Claxton (European Journal of Plant Pathology, 1999)

Aryl Ester Prodrugs of Cyclic HPMPC. I: Physicochemical Characterization and In Vitro Biological Stability - Reza Oliyai; Jeng-Pyng Shaw; Cathy M. Sueoka-Lennen; Kenneth C. Cundy; Murty N. Arimilli; Robert J. Jones; William A. Lee (Pharmaceutical Research, 1999)

Evidence for Environmental Sex Determination in the American eel, Anguilla rostrata - William H. Krueger; Kenneth Oliveira (Environmental Biology of Fishes, 1999)

Integration specificity of the hobo element of Drosophila melanogaster is dependent on sequences flanking the integration site - Kenneth J. Saville; William D. Warren; Peter W. Atkinson; David A. O'Brochta (Genetica, 1999)

Cryo-electron microscopy of GDP-tubulin rings - William V. Nicholson; Minou Lee; Kenneth H. Downing; Eva Nogales (Cell Biochemistry and Biophysics, 1999)

Screening of fungal species for fumonisin production andfumonisin-like disruption of sphingolipid biosynthesis - William P. Norred; Charles W. Bacon; Ronald T. Riley; Kenneth A. Voss; Filmore I. Meredith (Mycopathologia, 1999)

Long-term Observations for Monitoring Extremes in the Americas - David R. Easterling; Henry F. Diaz; Arthur V. Douglas; William D. Hogg; Kenneth E. Kunkel; Jeffry C. Rogers; Jaime F. Wilkinson (Climatic Change, 1999)

A root-injection method to assess verticillium wilt resistance of peppermint ( Mentha × piperita L.) and its use in identifying resistant somaclones of cv. Black Mitcham - Kenneth C. Sink; William E. Grey (Euphytica, 1999)

Evaluation of the Barr & Stroud FP15 and Criterion 400 Laser Dendrometers for Measuring Upper Stem Diameters and Heights - Michael S. Williams; Kenneth L. Cormier; Ronald G. Briggs; Donald L. Martinez (Forest Science, 1999)
Calibrated Barr & Stroud FP15 and Criterion 400 laser dendrometers were tested for reliability in measuring upper stem diameters and heights under typical field conditions. Data were collected in the Black Hills National Forest, which covers parts of South Dakota and Wyoming in the United States. Mixed effects models were employed to account for differences between users of the dendrometers and to test for significant differences between the heights and diameters measured indirectly (by dendrometer) and directly (by caliper and linear tape). The location at which measurements were taken on each tree was determined by paint marks along the bole. No significant differences between users were found. The Barr & Stroud consistently overestimated diameters by approximately 0.3 cm (0.1 in). Unbiased estimates of diameter were obtained with the Criterion 400. For height measurements, neither the Barr & Stroud nor the Criterion 400 produced unbiased measurements. The effect of distance to the base of the tree and height of the diameter measurement on the variability of the measurements was also studied. As distance increased, the variability of diameter measurements increased for both dendrometers. For the measurement of height, only the Barr & Stroud exhibited an increase in the variability of measurements with increasing distance. After correcting the data for their biases, taper equations were fitted to them and analyzed. The equations generated from the Barr & Stroud were not significantly different from those generated from direct measurement, unlike the Criterion 400 where taper equations generated were statistically different. A brief study of the effects of familiarity with each dendrometer indicated that the measurement error and variability decreased as the user became more familiar with the Criterion. This was not the case for the Barr & Stroud. For. Sci. 45(1):53-61.

Survival and Growth of Seedlings of Four Bottomland Oak Species in Response to Increases in Flooding and Salinity - William H. Conner; Kenneth W. McLeod; James K. McCarron (Forest Science, 1998)
Four oak species representing a range of flood tolerance were chronically (simulating sea level rise) and acutely (simulating hurricane storm surge) exposed to increased flooding and salinity in a complete factorial experiment. Survival, growth, and final biomass were measured to assess differential species' responses. No Nuttall or overcup oak seedlings died when flooded with fresh water, but 10% of the swamp chestnut and 35% of the water oaks died. Floodwater salinities of 2 and 6 g L-1 resulted in mortality of all seedlings of all four species. Watering with 2 g L-1 saline water did not cause any mortality although leaf browning was evident in all species. Overcup oak seedlings were the most tolerant to watering with 6 g L-1 saline water (100% survival), while the other three species had high mortality. Increased salinity, both in watered and flooded conditions, generally resulted in decreased diameter growth and decreased root and shoot biomass. Short-term increases in salinity (simulated storm surge) resulted in total mortality of flooded seedlings, while drained seedlings recovered and leafed out the following spring. Results indicate that these bottomland oak species would be seriously affected by increased flooding and salinity from either hurricane storm surges or sea level rise. For. Sci. 44(4):618-624.

Conservation of Pacific Salmon: Response to Wainwright and Waples - Kenneth P. Currens; Fred W. Allendorf; David Bayles; Daniel L. Bottom; Christopher A. Frissell; David Hankin; James A. Lichatowich; Patrick C. Trotter; Thomas A. Williams (Conservation Biology, 1998)

A global survey of haplotype frequencies and linkage disequilibrium at the DRD2 locus - Kenneth K. Kidd; Bharti Morar; Carmela M. Castiglione; Hongyu Zhao; Andrew J. Pakstis; William C. Speed; Batsheva Bonne-Tamir; Ru-Band Lu; David Goldman; Chaeyoung Lee; Yong Suk Nam; David K. Grandy; et al. (Human Genetics, 1998)

BG-1 ovarian cell line: An alternative model for examining estrogen-dependent growth in vitro - William S. Baldwin; Sylvia W. Curtis; Clay A. Cauthen; John I. Risinger; Kenneth S. Korach; J. Carl Barrett (In Vitro Cellular & Developmental Biology - Animal, 1998)

Flood and salinity stress of wetland woody species, buttonbush (Cephalanthus occidentalis) and swamp tupelo (Nyssa sylvatica var.biflora) - James K. McCarron; Kenneth W. McLeod; William H. Conner (Wetlands, 1998)

In vivo effects of fumonisin B1-producing and fumonisin B1-nonproducing Fusarium moniliforme isolates are similar: Fumonisins B2 and B3 cause hepato- and nephrotoxicity in rats - Kenneth A. Voss; Ronald D. Plattner; Ronald T. Riley; Filmore I. Meredith; William P. Norred (Mycopathologia, 1998)

Metabolism and Pharmacokinetics of Novel Oral Prodrugs of 9-[(R)-2-(phosphonomethoxy)propyl]adenine (PMPA) in Dogs - Jeng-Pyng Shaw; Cathy M. Sueoka; Reza Oliyai; William A. Lee; Murty N. Arimilli; Choung U. Kim; Kenneth C. Cundy (Pharmaceutical Research, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Water Quality Functions of Riparian Forest Buffers in Chesapeake Bay Watersheds - Richard Lowrance; Lee S. Altier; J. Denis Newbold; Ronald R. Schnabel; Peter M. Groffman; Judith M. Denver; David L. Correll; J. Wendell Gilliam; James L. Robinson; Russell B. Brinsfield; Kenneth W. Staver; William Lucas; et al. (Environmental Management, 1997)

Interleukin 2 promoter/enhancer controlled expression of a synthetic cecropin-class lytic peptide in transgenic mice and subsequent resistance to Brucella abortus - WILLIAM A. Reed; PHILIP H. Elzer; FRED M. Enright; JESSE M. Jaynes; JOHN D. Morrey; KENNETH L. White (Transgenic Research, 1997)

Effects of nitrogen supply and continuous darkness on growth and photosynthesis of the arctic kelp Laminaria solidungula - William J. Henley; Kenneth H. Dunton (Limnology and Oceanography, 1997)
Sporophytes of the arctic kelp Laminaria solidungula were collected from the Beaufort Sea and kept for 7 months at 0±1.5°C in a factorial experiment under two light (continuous darkness or 25 µ mol photons m −2 s −1 on a 12: 12 L/D cycle) and two nutrient regimes (with or without added nitrate). We monitored growth rate and at the end of the experiment measured the following on both new and old blades: carbon and nitrogen content, chlorophyll and carotenoids, photosynthetic light‐response ( P vs. I ) curves, and photosynthetic unit size (Chl/P 700 ). New blade initiation was independent of light and external nitrate, but blades grew minimally in darkness. Both new (B1) and old (B2) blades of plants held in darkness (with or without added nitrate) had the same quantum yield ( ϕ m ) and area‐normalized photosynthetic capacity ( P m ), but a slightly lower respiration ( R d ) and compensation irradiance ≤ 1.5 µ mol photons m −2 s −1 ) as B2 of plants grown in the light with added nitrate. Nitrogen starvation in the light, but not in darkness, caused reduced pigments, Pm , and ϕ m , and increased I c . Tissue C and N were primarily affected by light, whereas pigments were more strongly affected by N and lightXN interaction. Based on these results, previous results for field‐collected plants, and continuous in situ light data, we conclude that total annual growth in this population is severely light‐limited, with N having an important but secondary role.

Prioritizing Pacific Salmon Stocks for Conservation - Fred W. Allendorf; David Bayles; Daniel L. Bottom; Kenneth P. Currens; Christopher A. Frissell; David Hankin; James A. Lichatowich; Willa Nehlsen; Patrick C. Trotter; Thomas H. Williams (Conservation Biology, 1997)
Over 300 native stocks of Pacific salmon, steelhead, and coastal cutthroat trout (Oncorhynchus spp.) are at risk of extinction in the Pacific Northwest. With only limited resources available for conservation and recovery, prioritization of these stocks may become necessary if meaningful measures are to be implemented. We propose criteria by which prioritization may be guided. First, we rank stocks for risk of extinction, either by population viability analysis or by a set of surrogate measures. Then we rank stocks for biological consequences of extinction, using sets of questions designed to establish the genetic and evolutionary consequences and the ecological consequences if a stock were to become extinct. Together, these rankings allow stocks to be prioritized for a range of possible actions, with those stocks at highest risk and bearing the greatest biological consequences of extinction receiving attention first. Application of the prioritization process to 20 Pacific anadromous salmonid stocks worked as intended, although data limitations are considerable. The process is most likely to work successfully when applied to many stocks on which data exist, when several experts carry out the prioritization, and when the results are peer reviewed.

Proposed methods for the measurement of regional renal blood flow using heat transfer analysis - Thomas Adams; William S. Spielman; Kenneth R. Holmes; S. R. Heisey; Michael M. Chen (Annals of Biomedical Engineering, 1985)

Homing behavior of wood thrushes (Hylocichla mustelina) - Kenneth P. Able; William F. Gergits; Jeffrey D. Cherry; Scott B. Terrill (Behavioral Ecology and Sociobiology, 1984)

Altered purine and pyrimidine metabolism in erythrocytes with purine nucleoside phosphorylase deficiency - Irving H. Fox; Jan Kaminska; N. Lawrence Edwards; Erwin Gelfand; Kenneth C. Rich; William N. Arnold (Biochemical Genetics, 1980)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)